Genome-wide association study reveals acute mountain sickness susceptibility in Chinese population - Xiangyi Zheng; Wenyu Song; Yuanfeng Li; Nandi Bao; Wenhui Li; Yang Liu; Juanjuan Liu; Bin Li; Xi Yang; Xiaobo Han; Jialin Wu; Liqun Ma; et al. (Molecular Genetics and Genomics, 2026)

From real-world trajectory-level pre-crash data to driving behavior modeling: An inverse reinforcement learning framework based on ghost-probe scenarios - Jiang Bian; Helai Huang; Zhiyuan Wei; Hanchu Zhou; Min Liu; Gui Gui; Rui Zhou (Travel Behaviour and Society, 2026)

Solvent-triggered dissolution-gelation for multiscale structural densification of lignocellulosic biocomposites - Yifan Guo; He Zhang; Tongxin Bian; Xiufang Ma; Xiu Dong; Rui Fan; Wei Wei; Yun Wan; Bin Yang; Zuowan Zhou (Chemical Engineering Journal, 2026)

Interfacial engineering of quinoa protein-guar gum complexes for 3D printable Pickering emulsions: Rheological modulation, structural fidelity, and lipophilic bioactive delivery - Rui Wang; Haizhen Mo; Zhenbin Liu; Menglin Zhang; Haipeng Ren; Lishan Yao; Shurui Peng; Xiaoling Zhu; Wei Zhou; Jiayi Zhang (Carbohydrate Polymers, 2026)

A review of atmospheric black carbon research progress in China - Qi Zhou; Shunyao Wang; Shujun Bie; Junjie Cai; Yingjun Chen; Yuan Cheng; Xiang Ding; Jianwei Gu; Jie Li; Weijun Li; Dantong Liu; Jiaying Liu; et al. (Atmospheric Environment, 2026)

Characteristics and sources of organic vapors during O3 pollution in a megacity Wuhan in China: from hydrocarbons to highly oxidized molecules - Chong Liu; Xiaoxiao Li; Haoqian Wang; Linjun Li; Ning Ma; Xinchi Ye; Shan Xu; Jian Tan; Jin Peng; Rui Xia; Yi Zheng; Feiyue Mao; et al. (Atmospheric Environment, 2026)

Differential effects of conventional and biodegradable microplastics on carbon and nitrogen transformation and greenhouse gas emissions in Cd-contaminated riparian sediments: Responses of microbial community structure - Haojie Chen; Danlian Huang; Wei Zhou; Yang Lei; Hai Huang; Lingshi Yin; Ruihao Xiao; Rui Deng; Guangfu Wang; Wenbo Xu (Water Research, 2026)

Cadmium induced ferroptosis of TM4 cells through PERK-ATF4-CHOP signaling pathway - Xuan Li; Juan Dai; Jiaoyang Wei; Yan He; Yue Han; Ting Zhou; Rui Li; Ling Zhang; Yuqin Shi (Reproductive Toxicology, 2026)

Critical review on strategies for the removal of antibiotics from water and wastewater: Present situation, challenges, and perspective - Ruiwu Zhou; Wei Pan; Weichao Huang; Ping Yu; Binrui Chen; Ruizhe Zhao; Lirong Chen; Rui Tang (Process Safety and Environmental Protection, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Magnetite-phase steel slag-peroxymonosulfate promoted volatile fatty acids recovery from anaerobic fermentation of food waste: Substrates structure disruption and metabolic regulation - Xiupeng Jiang; Wei Wang; Youcai Zhao; Wenxiao Zhang; Xi Li; Rui Zhang; Xiaoya Li; Tao Zhou (Journal of Environmental Chemical Engineering, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

Composite beeswax-glycerol monolaurate oleogelation enhances encapsulation efficiency and oxidative stability of microencapsulated Antarctic krill oil - Xin Sun; Liang Song; Rui-Ying Wang; Xin-Yang Ha; Fa-Wen Yin; Lei Qin; Bei-Wei Zhu; Da-Yong Zhou (Food Research International, 2026)

Molecular engineering of thermodynamic anchoring sites enables ultra-stable and high-capacity biomass hydrogels for atmospheric water harvesting - Jun Xia; Rui Yang; Xiaoke Li; Xinrong Huang; Size Zheng; Yingtang Zhou; Lihong Zhou; Wei Wang (Chemical Engineering Journal, 2026)

Aerobic extracellular electron transfer in Shewanella spp. - Wei Chen; Biyi Zhao; Liping Dai; Junpeng Li; Rui Bai; Fan Yang; Xudong Zhou; Jens Ulstrup; Feng Zhao; Yong Xiao (Bioresource Technology, 2026)

Increasing carbon emissions despite declining burned area in the Northern Hemisphere wildfires - Rui Shi; Yuhui He; Ruitong Guo; Xiaofan Wang; Yaliang Hou; Yue Zhou; Xiaoying Niu; Hui Wen; Jun Liu; Wei Pu; Xin Wang; Dongyou Wu (Atmospheric Research, 2026)

Characteristics and source analysis of fluorescent aerosol particles at a typical rural site in the North China Plain during autumn and winter - Yang Zhou; Wei Hu; Siyao Yue; Wanyun Xu; Rui Jin; Boran Hua; Zihe Li; Libin Wu; Junjun Deng; Jiangchuan Tao; Nan Ma; Hang Su; et al. (Atmospheric Environment, 2026)

The role of HMGB1 in vascular endothelial cells - Duzhe Jiang; Ye Zhou; Junying Duan; Wei Zhong; Junjie Liu; Rui Chen; Wei Yuan (Apoptosis, 2026)

Single-cell transcriptomic analysis identifies a MIF-driven keratinocyte-macrophage-Th2 axis as a key inflammatory circuit in atopic dermatitis - Yan Wei; Rui-Min Bai; Hao-Ran Guo; Jin Shan; Li-Juan Wang; Yan Zhou; Kuan-Hou Mou; Yan Zheng; Ya-Guang Zhang (Inflammation Research, 2026)

Retention of water ice in lunar permanent shadowed regions - Sunpeng Zhou; Zhenpeng Wang; Shanshan Zhou; Hang Deng; Qinggong Wang; Rui Wu; Wei Yao; Ke Xu (Icarus, 2026)

Melatonin treatment improves chilling tolerance and maintains quality of postharvest Actinidia arguta fruit by regulating membrane lipid metabolism - Rui Wu; Xinqi Liu; Feiyang Wang; Shiwei Li; Baodong Wei; Qian Zhou; Yang Sun; Shunchang Cheng (Food Chemistry, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

Genome-wide association analysis and candidate gene identification for plant height in Shanxi local foxtail millet varieties - Wei Zhou; Huibin Qin; Haigang Wang; Hui Zhi; Rui Huang; Sen Hou; Junjie Wang; Ling Chen; Xiang Tian; Zhijun Qiao; Zhixin Mu; Xianmin Diao (Theoretical and Applied Genetics, 2026)

Fungal-driven carbon sequestration within soil aggregates under paddy multicropping - Wei Zhang; Wen Liu; Leyan Zhang; Mengyao Zhou; Rui Xiong; Hongling Qin; Anlei Chen; Baoli Zhu; Zhiqiang Fu; Pan Long (Applied Soil Ecology, 2026)

Facilitating group consensus for offshore oil and gas decommissioning options: An improved similarity-based model - Xin Wei; Ming Li; Rui Li; Jin Zhou (Journal of Cleaner Production, 2026)

Manganese oxide reduction by non-extracellular respiratory bacteria and fraxetin from plant residues decomposition - Wei Chen; Rui Bai; Xudong Zhou; Biyi Zhao; Chongyuan Ren; Junpeng Li; Liping Dai; Yacen Fang; Jing Zhang; Andreas Kappler; Feng Zhao; Yong Xiao (Journal of Environmental Sciences, 2026)

Associations between domestic water hardness and incident type 2 diabetes and the mediating role of metabolomics - Hanwen Zhou; Sicheng Li; Keyang Li; Wenlong Li; Yingcheng Liu; Rui Yu; Xufeng Xian; Wei Zheng; Xiaoni Zhong; Biao xie (Environmental Pollution, 2026)

Transdermal delivery of small zwitterionic amorphous solid dispersion to increase solubility and penetrate the stratum corneum for psoriasis therapy - Xiang Zhou; Jiahui Ma; Lanlan Wang; Dongyu Zhang; Dongyue Ding; Rui Xu; Ke Wang; Junlong Qi; Yinan Zhong; Dechun Huang; Wei Chen (Chemical Engineering Journal, 2026)

Corrigendum to: “Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury” [Chem. Eng. J. 524 (2025) 169698] - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2026)

Dual Low-b-value-driven U-shaped fusion GAN for synthesizing high-b-value prostate DWI - Rui Feng; Qun Huang; Aiping Chen; Chuanbing Wang; Leilei Zhou; Jingjing Xu; Xiaodong Wang; Da Cao; Xiuhan Li; Wei Wang (Physical and Engineering Sciences in Medicine, 2026)

Depth-dependent phosphorus leaching risks in littoral soils of Lake Dianchi under extreme rainfall - Leibo Ding; Wenbin Zhou; Rui Liu; Kaimin Shih; Xingyu Deng; Xiaoyi Bi; Wei Ma (Environmental Geochemistry and Health, 2026)

Characteristics and Genesis of Fine-Grained Clastic Reservoirs in the Huangliu Formation Ultra-Low-Pressure Permeable Gas Reservoir in the Dongfang Area of Yinggehai Basin - Wei Zhou; Hui Zhang; Chong Zhang; Di Meng; Yao Guan; Lijuan Qin; Rui Yang (Journal of Ocean University of China, 2026)

Triphasic volatile emission dynamics and gene expression in postharvest PGF-lost non-melting peach (Prunus persica) var. RedY - Ping Zhou; Xiaodan Zhang; Xin Feng; Rui Guo; Shaobin Yan; Xiuqing Wei; Liang Li; Yajun Tang; Zhizheng Fang; Yan Lei (Postharvest Biology and Technology, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

Regulating proton migration by trace additive for ultra-stable Zn anodes - Yaowen Xu; Zhao Chen; Shaofei Wu; Rui Zhao; Qiao Luo; Xuanyuan Liao; Yaqin Wu; Yiman Xie; Wei Zhang; Liangjun Zhou; Weifeng Wei (Chemical Engineering Journal, 2026)

Redox-active antioxidants enable highly stable bio-electrochemical systems - Wei Chen; Rui Bai; Biyi Zhao; Xudong Zhou; Feng Zhao; Yong Xiao (Bioresource Technology, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

Responses of soil nitrogen mineralization to ecological restoration-oriented constructed grasslands with different recovery ages in the Three-River Headwaters Region - Jie Zhu; Baolin Li; Guoyi Zhou; Yecheng Yuan; Wei Liu; Rui Li; Qiuyuan Tan; Qingling Sun (Plant and Soil, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Integrating distributed hydrologic simulation with low-flow resilience: a spatiotemporal perspective - Yan Zhou; Chi Zhang; Rui Hao; Yongxin Liao; Wei Yin; Dianchang Wang (Journal of Hydrology, 2026)

Insight into the enhancement effect of pristine and amino-functionalized MWCNTs@SiO2 on the CO2 absorption and solar-driven regeneration performance of alkaline deep eutectic solvent based nanofluid system - Wei Wang; Yang Tang; Yi-Ming Chen; Rui-Rui Zhou; Zhang-Mao Hu; Jin-Cheng Huang (Journal of Environmental Chemical Engineering, 2026)

Surface aging of Ti-based MXene attenuates mitochondrial toxicity via suppressed cellular uptake and reactivity - Rui Zhang; Xiaodi Li; Yujiao Liu; Xuan Mao; Yongyi Wei; Yu Wang; Xiaofei Zhou; Jianbo Jia (Environmental Pollution, 2026)

Zircon thermal annealing ages determine a late Eocene birth for the First Bend of the Yangtze River - Yang Zhang; Rui Li; Guang-Yan Zhou; David Chew; Jian-Ping Zheng; Qing Xiong; Wei Wang (Earth and Planetary Science Letters, 2026)

Binasal occlusion modulates cortical functional connectivity and hemodynamics in acquired paralytic esotropia: a fNIRS study - Jie Zhou; Ran Du; Xue Wang; Jun Wu; Fubiao Huang; Rui Fang; Yixiong Liang; Ning Song; Wenbin Wei (Experimental Brain Research, 2026)

Establishment and application of multiple cross displacement amplification coupled with lateral flow biosensor (MCDA-LFB) for visual and rapid detection of Candida glabrata - Yan Yuan; Yuhong Zhou; Yanfeng Zhou; Rui Ye; Jingrun Lu; Yizhe Wang; Fang Wei; Fukuan He; Honglan Yu; Yu Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Highly transparent sponge-like hydrogel substrates regulated by NaCl for efficient solar water evaporation - Ke Cheng; Yangyang Li; Hong Ni; Rui Zhang; Wei Wei; Jing Zhou; Jing Yuan (Chemical Engineering Journal, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

Genomic evidence resolves species identity and hybridization in farmed Golden pompano (Trachinotus anak) - Liang Guo; Siqing Wang; Jiehong Wei; Rui Peng; Zhongyuan Shen; Luojing Zhou; Jiaxuan Kang; Ke Rao; Yang Yang; Zhennian Chen; Chang Wu (Aquaculture, 2026)

Roles of vertical light-conducting carriers applied in microalgal-bacterial biofilm for enhanced nitrogen and phosphorus removal - Yong-Sen Cao; Yong-Qi Cheng; Yi Liu; Xing-Rui Zhou; Cong-Cong Tang; Zhang-Wei He; Wen-Qiong Wang; Yu Tian; Xiaochang C. Wang (Bioresource Technology, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Stronger Adaptability of Eukaryotic Communities than Prokaryotes in Seawater across an Extensive Salinity Gradient - Shan Gao; Wei Zhao; Xiaoyan Guan; Zelong Zhao; Bai Wang; Yao Xiao; Guohan Zhang; Yongjia Pan; Hongjuan Sun; Pingzhe Jiang; Rui Mi; Jingwei Jiang; et al. (Marine Biotechnology, 2026)

Sevoflurane-induced ferroptosis in developing neurons mediated by the NCOA4-ferritinophagy-GPX4 pathway - Cheng-Yi Lao; Wei-Xin Dai; Jie-Chao Zhou; Rui-Ping Huang; Huan Feng (Journal of Molecular Histology, 2026)

Identification of disease-associated gene expression signatures for mechanistic insights and drug prediction in dilated cardiomyopathy-induced heart failure - Wei Yu; Shuai Xu; Xin Tan; Hangyao Zhang; Ruohan Ma; Yiyao Zeng; Anchen Xu; Honghui Tang; Qin Rui; Yahui Song; Yafeng Zhou (Molecular and Cellular Biochemistry, 2026)

Tectonic uplift of the western segment of the East Kunlun Mountains since early Miocene times: Constraints from detrital zircon fission track geochronology and subsurface data - Yadong Wang; Wei Zhou; Sihua Yuan; Yuan Rui (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Beyond the surface: how dissolved organic matter recasts the biogeochemical behaviors of micro- and nanoplastics in aquatic environments - Haojie Chen; Danlian Huang; Ruihao Xiao; Wei Zhou; Lingshi Yin; Rui Deng; Hai Huang; Yang Lei; Ruijin Li (Gondwana Research, 2026)

Vacuolar K⁺ efflux transporter TaTPK1-5D confers low-K⁺ tolerance of ‘Zhengmai 136’ through interaction with TaCIPK23-4D in bread wheat - Yingna Feng; Qianni Wei; Sisi Sun; Hongbing Zhang; Ting Zhou; Rui Cui; Wenxu Li; Yunqi Liu; Yingpeng Hua; Zhengfu Zhou (Theoretical and Applied Genetics, 2026)

Development of an environmentally sustainable composite incorporating phosphogypsum aggregate: a perspective for enhancing interfacial stability - Shiyuan Fu; Chiqiu Wu; Wei Lv; Yuan Feng; Xue Liu; Yuxin Zhou; Kangning Liu; Rui Yu (Innovative Infrastructure Solutions, 2026)

Whole-genome resequencing unveils the phylogeographic coevolution of Oncomelania hupensis with Yangtze River dynamics in China - Lei Duan; Fang Luo; Qin Liu; Shen Chen; Xia Tian; Wen-Wen Lv; Lu He; Zi-Rui Ren; Jing Xu; Xiao-Nong Zhou; Shi-Zhu Li; Shan Lv; et al. (Molecular Phylogenetics and Evolution, 2025)

Quantifying nitrogen loss responses to seasonal deluges and droughts: A modeling study in a subtropical agro-forest catchment, upper Yangtze River - Wei Zhang; Xunhua Zheng; Siqi Li; Chunyan Liu; Zhisheng Yao; Shenghui Han; Rui Wang; Kai Wang; Bo Zhu; Minghua Zhou; Xiao Chen; Yong Li (Ecohydrology & Hydrobiology, 2025)

Dual-mechanism defect engineering of multi-enzyme embedded ZIF-8 for efficient anthocyanin extraction from black rice - Mengyuan Cao; Bicong Wang; Yuchao Deng; Da-Wei Pan; Xiao-Jie Ju; Rui Xie; Zhuang Liu; Xing-Long Zhou; Mao-Jie Zhang; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2025)

Upcycling PET waste into carbon quantum dots as flame retardant of PET for closed-loop recycling - Jianfei Wei; Guocong Ma; Yaoyao Tang; Jing Zhang; Gaoling Jin; Chaohui Ma; Linhan Bing; Zhiguo Zhu; Zhenfeng Dong; Puzhen He; Ruichen Zhou; Rui Wang; et al. (Chemical Engineering Journal, 2025)

Retraction notice to “A bioactive dextran-based hydrogel promote the healing of infected wounds via antibacterial and immunomodulatory” [Carbohydrate Polymers 291 (2022) 119558] - Lisheng Zhou; Liming Zhou; Chengxiu Wei; Rui Guo (Carbohydrate Polymers, 2025)

Mechanistic insights into Schisandrin C as the active anti-renal fibrosis ingredient of Schisandra chinensis: a network pharmacology analysis and transcriptomics integrated experimental verification - Xinping Yang; Xijier Qiaolongbatu; Rui Shen; Yuting Wang; Wenjing Li; Li Wang; Chunyan Zhou; Taishan Wei; Zhenghua Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Deep structure of the middle segment of the Bangong-Nujiang Suture Zone based on aerogravity and aeromagnetic anomalies, Qinghai-Tibet Plateau - Bao-bao Cao; Dao-qing Zhou; Yan-yan Wei; Rui Zhao; Qiao-juan Yan; Lei Xu; Di-shuo Zhang (Applied Geophysics, 2025)

Microplastics modulate neutrophil migration via an ROShistone lactylation positive feedback loop - Yi-li Wang; Xiao-chen Yuan; Chun-jiao Wei; Ke-yun Li; Lin-xi Zuo; Hao-yi Zhang; Rui-chen Ding; Ren Zhou; Yun-hua Zhang; Da-long Ren (Journal of Hazardous Materials, 2025)

Multi-omics investigation unveils the role of Eurotium cristatum fermentation in potentiating thinned young apple pomace for colitis-induced liver disorders amelioration - Jiayao Lv; Yi Wang; Lanqi Zhou; Shiyi Zhang; Wei Song; Rui Dong; Tianqi Liu; Guoze Wang; Lin Shi (Food Research International, 2025)

Insights into the key odorants in Chimonanthus praecox var. concolor Mak. Flower using the sensomics approach - Peng Guo; Wei Guan; Runhu Xin; Yuanhao Zhou; Miao Liang; Yajian Wu; Rui Wang; Yuping Liu (Food Chemistry, 2025)

Core microbiota with antimonite oxidation coupled nitrogen fixation traits persist in the rhizosphere of pioneer plants in antimony tailings - Hanbing Gao; Zhaohui Guo; Fenglian Huang; Shikai Li; Xiao He; Jaovola Ulrich Fernio; Wei lv; Ling Zhou; Shuyang Du; Min Shen; Rui Xu (Environmental Research, 2025)

A carrier-assisted strategy for accelerating aerobic granulation under low superficial gas velocity: Critical contributions of sediment biochar and camellia shell biochar carriers - Qingxia Lin; Chuxuan Song; Jun Li; Ziqiang Liu; Xue Hu; Rui Xue; Suiqin Yang; Yang Gao; Wei Zhang; Lean Zhou; Julong Sun; Jinting Wang; et al. (Environmental Research, 2025)

Sequential targeted nanomedicine MPC treats cerebral ischemia-reperfusion injury via neuronal microenvironment reprogramming - Shuya Wang; Ruishi Li; Xiaojing Shi; Tingli Xiong; Wenxuan Zheng; Weimin Qi; Min Liu; Lin Dai; Qian Lin; Rui Huang; Wei Dai; Min Zhou; et al. (Chemical Engineering Journal, 2025)

Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2025)

Magnetic biochar-cored halophilic aerobic granules: Novel strategy for rapid formation and structural stability enhancement - Dong-Xu Zhou; You-Wei Cui; Ya-Nan Mi; Zhen-Ying Li; Rui-Chun Yang; Yuan Sui (Bioresource Technology, 2025)

Cassiterite U–Pb ages from the Tin Islands, Indonesia, the southern end of the Southeast Asian tin province - Jie-Hua Yang; Rui-Zhong Hu; Mei-Fu Zhou; Bernd Lehmann; Jun-Hong Zhao; Jing-Hua Wu; Liang Liu; Wei Mao; Zheng-Teng Cui; Mega Fatimah Rosana (Mineralium Deposita, 2025)

Constraints of in-situ elemental and B isotopic compositions of tourmaline on the origin of the Nong Sua Sn deposit, Thailand - Jie-Hua Yang; Rui-Zhong Hu; Liang Liu; Wei Mao; Ya-Zhou Fu; Mei-Fu Zhou; Heng Chen; Alongkot Fanka; Ke-Jun Hou (Mineralium Deposita, 2025)

Greenhouse Gas Footprints of Maize Cultivation Systems in Different Climate Zones: Field Data Validation and Application of CNMM–DNDC as a Hydro-Biogeochemical Model - Siqi Li; Wei Zhang; Yong Li; Chunyan Liu; Bo Zhu; Job Kihara; Peter Bolo; Zhisheng Yao; Kai Wang; Shenghui Han; Rui Wang; Jiarui Sun; et al. (Advances in Atmospheric Sciences, 2025)

Calibration of the Edinburgh Elasto-Plastic Adhesion contact model for modelling clay-moist soil with high moisture content - Xuan Deng; Wencheng Wu; Jiawei You; Rui Jiang; Mengliang Li; Ju Li; Youfeng Tao; Hong Cheng; Wei Zhou; Fei Deng; Yong Chen; Wanjun Ren; et al. (Computers and Electronics in Agriculture, 2025)

Vitamin E alleviates ammonia‑nitrogen and hypoxia co-exposure-induced intestinal damage in grass carp (Ctenopharyngodon idella) by modulating mitochondrial function, cellular autophagy and apoptosis - Rui Su; Ke Yao; Xiao-Qiu Zhou; Lin Feng; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Hong-Mei Ren; Xiao-Wan Jin; Pei Wu (Aquaculture, 2025)

Metagenomic insights into the synergistic properties and mechanisms of sludge microbial communities degrading polystyrene and polypropylene - Ying Zhou; Wei-hua Gu; Jian-feng Bai; Rui-xue Wang; Cheng-long Zhang; Yao-guang Guo; Cong Lu; Shan-ping Chen (Journal of Hazardous Materials, 2025)

Endothelial HMGB1-AIM2 axis worsens myocardial ischemia—reperfusion injury by regulating endothelial pyroptosis - Rui Chen; Junying Duan; Ye Zhou; Mengfei Cao; Ye Su; Duzhe Jiang; Aibin Tao; Wei Yuan; Zhiying Dai (Apoptosis, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Silicon supplementation via carriers to enhance diatom competition with cyanobacterial blooms and remediate eutrophic waters - Rui Zhou; Bang Xiao; Li Zhao; Yangyang Tang; Wei Yang; Huazu Liu; Xiangdong Zhang; Chaowei Yuan; Xinqi Wang; Xizi Long; Qiang He; Wei Li (Water Research, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

6,7-Dimethoxy-3H-Quinazolin-4-One as a dual-function inhibitor of polyphenol oxidase and bacteria: biological evaluation, mode of action, and anti-browning studies - Xiu-Zhen Li; Jin-Rui Qiao; Yi-Rui Wu; Dong-Yan Zhou; Yu-Dan Shi; Shu-Meng Zhu; Qiu-Han Bai; Xiao-Lei Xia; Wei-Ming Chai (Food Bioscience, 2025)

Synergistic integration of photoelectron utilization and by-product pathway suppression for microbial production of bacitracin - Rui Bai; Wei Chen; Xudong Zhou; Junpeng Li; Yi He; Yong Xiao; Feng Zhao (Chemical Engineering Journal, 2025)

Anion competitive coordination for solvation structure regulation in high-voltage sodium-ion batteries - Bowen Zhu; Jingkai Gao; Simin Li; Wei Zhou; Zhendong Yang; Rui Jin; Yi Zhang; Zixuan Ding; Yanqing Lai; Jie Li; Zhian Zhang (Chemical Engineering Journal, 2025)

Hydrogen jet fire due to high-pressure pipeline leakages in pits - Kuibin Zhou; Qinyun Zhou; Xizhen Wang; Wei Wang; Zilong Rui; Juntao Yang (Process Safety and Environmental Protection, 2025)

A series of meroterpenoids with highly oxygenated skeletons from the endophytic fungus Penicillium sp. and their anti-inflammatory activities - Tu-Xiang Mo; Liu-Xia Lv; Xi-Shan Huang; Jia-Tong Zhou; Qian Wu; Xian-Hua He; Li-Qi Liang; Wei-Feng Xu; Jun Li; Rui-Yun Yang (Phytochemistry, 2025)

Multifunctional Janus hydrogel targeting mitochondrial regulation and inflammatory pathways promotes infected burn wound repair - Xiaohui Li; Longbao Feng; Honglin Wu; Hao Yang; Peng Wang; Yongfei Chen; Yuxi Zhou; Jiayuan Zhu; Wei Xue; Rui Guo; Zhicheng Hu (Chemical Engineering Journal, 2025)

Alterations in microbial-mediated methane, nitrogen, sulfur, and phosphorus cycling within paddy soil induced by integrated rice-fish farming - Yiran Hou; Rui Jia; Linjun Zhou; Liqiang Zhang; Sun Wei; Bing Li; Jian Zhu (Journal of Environmental Management, 2025)

Multidimensional analysis of sensory perception and neurophysiological responses to marinated beef cooked by diverse methods - Tianyi Yang; Wei Jiang; Chencheng Luo; Jin Hu; Wei Xu; Peng Zhang; Xiaofei Jin; Yuxuan Zhou; Rui Liu; Zhiyu Qian; Yamin Yang (Innovative Food Science & Emerging Technologies, 2025)

Multifunctional amine salt additive for enhancing the performance of perovskite and perovskite/silicon tandem solar cells - Jun Qu; Wenfeng Zhang; Yangdi Chen; Huiyao Zhao; Yanbei Wei; Rui Zhou; Hongjie Wan; Jie Deng; Dongyong Fan; Yuchen Luo; Haijin Li (Chemical Engineering Journal, 2025)

Archean to early Mesoproterozoic crustal evolution of the Yangtze Craton: Insights from U-Pb-Hf-O isotopic and trace elemental compositions of detrital zircon - Xinyu Cai; Rui Li; Guangyan Zhou; Heng Luo; Zhifu Liu; Nimat Ullah Khattak; Wei Wang (Precambrian Research, 2025)

TiO2-SnO2-RuO2 electrode with enhanced chlorine evolution selectivity for acid electrolytic oxidized water preparation - Yifei Liu; Rui Zhou; Chunpu Cao; Zijian Lv; Xudong Liao; Yuanyuan Zhao; Longsheng Wu; Zhewen Lu; Daqing Wei (Journal of Environmental Chemical Engineering, 2025)

Volcanic CO2 emissions from subduction of the tropical Paleo-Tethyan Ocean contributed to the early Permian deglacial warming - Wei Feng; Jianghai Yang; Peter A. Cawood; Rui Ma; Yinsheng Zhou; Ying Cui (Earth and Planetary Science Letters, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Identification of antifungal metabolites from a soil-derived Streptomyces strain active against Fusarium graminearum using genome mining - Xingyu Liu; Lubna Rahman; Yang Zhang; Rui Guo; Min Zhang; Wei Zhou (Biotechnology Letters, 2025)

Multi-stage early Cretaceous magmatism in the Tongling region, lower Yangtze metallogenic belt (E. China) - Rui Zhao; Daoqing Zhou; Yuzhou Zheng; Baobao Cao; Yanyan Wei; Yue Hu; Mengchu Xiao; Xiawei Hu (International Geology Review, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Recovery of volatile ethanol gas via microalgal-bacterial consortium: Ethanol-to-acetate conversion pathway boosts lipid production - Liu-Xu Jiang; You-Wei Cui; Ya-Nan Mi; Dong-Xu Zhou; Ming-Teng Li; Rui-Chun Yang (Journal of Environmental Management, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Irpex lacteus metabolites ameliorate hyperlipidemic mice via CYP7A1/HMGCR/FXR/AMPK signalling pathways and gut microbiota - Xuan Zhang; Yanye Wei; Jincheng Wu; Yue Lu; Zhenxin Zhu; Chaonan Kong; Rui Zhou; Xianke Li; Lifang Yang; Mingguo Jiang (Food Bioscience, 2025)

Integrated rice-fish farming dynamically altered the metal resistances and microbial-mediated iron, arsenic, and mercury biotransformation in paddy soil - Yiran Hou; Rui Jia; Linjun Zhou; Liqiang Zhang; Wei Sun; Bing Li; Jian Zhu (Environmental Pollution, 2025)

Fabrication of flexible polymer-MOF composite electrolyte for solid-state lithium metal batteries with high rate performance - Jiansheng Gao; Yan Chai; Jialun Ni; Yong Zeng; Gaoyuan Zhang; Xueling Liu; De Ning; Xinghui Jin; Huajun Zhao; Dong Zhou; Rui Gao; Wei Wu; et al. (Chemical Engineering Journal, 2025)

A mammary gland secretion function exploratory study based on a quantitative comparison between milk and serum - Li long Wei; Rui Xiao; Yun Zhou; Cheng wu Han; Yong tong Cao (Molecular and Cellular Biochemistry, 2025)

TadpoleTraits : A Global Database on Morphological Traits of Tadpoles of Anura - Yanfang Song; Rui Tian; Yongle Wang; Pingfan Wei; Tao Zhang; Shuaiwei Luo; Zhiyong Yuan; Weiwei Zhou (Global Ecology and Biogeography, 2025)
Motivation Functional diversity is an important dimension of biodiversity. In animals, most species have complex life cycles, such that the same species can display great differences in traits and ecological roles across different life history stages. Consequently, the patterns and driving factors of functional diversity can vary considerably among the different life stages. However, research on stages other than adults is rare, with data scarcity being a potential reason. The order Anura of Amphibia is a highly diverse group of terrestrial vertebrates, comprising more than 7800 species. Anurans have complex life cycles, and our knowledge about functional traits of the larval stage is extremely limited. To fill this gap, we collected morphological traits of tadpoles globally and compiled a database covering 1993 species to facilitate future studies. This database can help us gain a more comprehensive understanding of anuran biodiversity. Additionally, it offers a valuable tool for testing ecological and evolutionary hypotheses related to complex life cycles in animals. Main Types of Variables Contained Twenty‐three traits collected from literature and 11 traits obtained by image measuring. Spatial Location and Grain Global. Major Taxa and Level of Measurement Anura, species. Software Format xlsx.

Gut microbiota’s role in high-altitude cognitive impairment: the therapeutic potential of Clostridium sp. supplementation - Wei Zhou; Yongqiang Zhou; Shikun Zhang; Bin Li; Zhong Li; Zhijie Bai; Dezhi Sun; Chaoji Huangfu; Ningning Wang; Tiantian Xia; Congshu Huang; Lina Guan; et al. (Science China Life Sciences, 2025)

Expanding glacial lakes and assessing outburst susceptibility of moraine-dammed lakes using logistic regression in the Yigong Tsangpo Basin, Tibet, China - Ziyang Yuan; Rui Wang; Wei Zhou; Ningsheng Chen; Runfang Liu; Jinzhu Mao; Tao Wang (Natural Hazards, 2025)

Unveiling the nonlinear relationships and co-mitigation effects of green and blue space landscapes on PM2.5 exposure through explainable machine learning - Wei Cao; Liyan Wang; Rui Li; Wen Zhou; Deshun Zhang (Sustainable Cities and Society, 2025)

Analysis of soil bacterial diversity and effective control of mango anthracnose - Xiaohu Wang; Shuang He; Rui Wang; Xin Liu; Tingting Mo; Qi fei Liu; Liujian Ye; Qixia Zhu; Shengbo Wei; Jianzong Meng; Hongmei Gao; Liqin Zhou (Physiological and Molecular Plant Pathology, 2025)

Migration and distribution of thallium related with lead-zinc smelting enterprises from raw materials to soil: In-situ insight using diffusive gradients in thin-films - Wenhao Wang; Siwei Deng; Jiang Yu; Yi Wu; Wenjuan Feng; Qin Fan; Rui Zhou; Peirou Li; Wei Deng; Zhi Huang; Jie Yu; Weiwei Zhu (Environmental Pollution, 2025)

Pareto-guided active learning for accelerating surrogate-assisted multi-objective optimization of arch dam shape - Rui Liu; Gang Ma; Fanhui Kong; Zhitao Ai; Kun Xiong; Wei Zhou; Xiaomao Wang; Xiaolin Chang (Engineering Structures, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Recombinant Human Nerve Growth Factor Integrated Hyaluronic Acid Hydrogel Microneedles for Corneal Nerve Repairing - Ziqing Feng; Rui Liu; Ruoyan Wei; Yunzhe Wang; Tianze Cui; Chang Liu; Xiaojun Hu; Chi Zhang; Bin Kong; Meiyan Li; Xingtao Zhou (Chemical Engineering Journal, 2025)

Anti-inflammatory effect of multi-dose tranexamic acid in hip and knee arthroplasty: a systematic review and meta-analysis of randomized controlled trials - Chen Rui; Guangchun Dai; Chuwei Tian; Shaoyang Zhou; Yucheng Gao; Mumin Cao; Wei Wu; Shengbo Qin; Yunfeng Rui (Inflammopharmacology, 2025)

Investigation on neutronics changes in tungsten granular blockage accident on VENUS-II light water reactor - Liang Chen; Wei Jiang; Zhao-Dong Xia; Fei Ma; Rui Yu; Hai-Yan Meng; Qi Zhou; Hong-Lin Ge; Yan-Bin Zhang; Xue-Ying Zhang (Annals of Nuclear Energy, 2025)

Monitoring nutrient and beneficial elements in the topsoil: the function of weathered background and later surficial process on their distribution - Bo Zhang; Kai-Ning Lv; Huan Li; Qin-Rui Zhang; Zhi-Qiang Yin; Wei-Zhi Zhou; Guo-Li Yuan (Environmental Monitoring and Assessment, 2025)

Expanding the pH range of Fenton-like reactions for pollutant degradation: The impact of acidic microenvironments - Shi-Lin Xu; Wei Wang; Yi Song; Rui Tang; Zhen-Hu Hu; Xiao Zhou; Han-Qing Yu (Water Research, 2025)

Corrigendum to “Differentiation of sow and mouse ovarian granulosa cells exposed to zearalenone in vitro using RNA-seq gene expression” [Toxicology and Applied Pharmacology, 350 (2018) 78–90] - Guo-Liang Zhang; Jun-Lin Song; Yi Zhou; Rui-Qian Zhang; Shun-Feng Cheng; Xiao-Feng Sun; Guo-Qing Qin; Wei Shen; Lan Li (Toxicology and Applied Pharmacology, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Electrically conductive hot mix asphalt mixtures for salt-free snow/ice-melting pavements heated with direct electric energy: A comparison between utilizing carbon-based aggregate and fiber - Yanhai Wang; Yucen Li; Wei Hu; Rui Xiao; Hongyu Zhou; Baoshan Huang (Journal of Cleaner Production, 2025)

Grazing increases the complexity of networks and ecological stochastic processes of mycorrhizal fungi - Jiqiong Zhou; Pengsen Wang; Li Wei; Jianguo Zhang; Xuxu Li; Nan Huang; Gang Liu; Kun Zou; Rui Fan; Lin Liu; Xiao Ma; Ting Huang; et al. (Journal of Environmental Management, 2025)

In-situ experiments of dynamic microscopic reaction for CO2-brine-carbonate system - Yulong Zhao; Yongchao Wang; Shaomu Wen; Liehui Zhang; Zhenglin Cao; Zihan Zhao; Wei Xiong; Cheng Cao; Rui Tang; Yunting Fan; Zehao Xie; Ruihan Zhang; et al. (Chemical Engineering Journal, 2025)

Programmable allosteric DNA nanomachine for ratiometric imaging of VEGF in tumor cells - Jia-Wei Liang; Yan-Mei Lei; Zhao-Peng Chen; Xue-Mei Zhou; Ya-Qin Chai; Ruo Yuan; Rui Du; Ying Zhuo (Chemical Engineering Journal, 2025)

Secular evolution of continental crust of the North China Craton constrained by U-Pb and Lu-Hf-O/Sm-Nd isotopic analyses of detrital zircon and monazite in river sediments - Guangyan Zhou; D. Graham Pearson; Yan Luo; Long Li; Christopher M. Fisher; Rui Li; Wei Wang; Yuanbao Wu (Chemical Geology, 2025)

Experiment study on vortex evolution process and vorticity distribution in wave boundary layer flow over a rippled bed - Shouqian Li; Shihuan Zhou; Yongjun Lu; Rui Hu; Wei Huang; J.A. Roelvink (Coastal Engineering, 2025)

Identification of multiple miRNA-encoded peptide reveals OsmiPEP162a putatively stabilizes OsMIR162 in rice - Jianping Zhou; Rui Zhang; Qinqin Han; Hongjun Yang; Wei Wang; Yibo Wang; Xuelian Zheng; Fan Luo; Guangze Cai; Yong Zhang (Plant Cell Reports, 2025)

In vivo quantification of polyphosphate in Microcystis aeruginosa using DAPI staining - Rui Zhu; Xiao Tan; Zhipeng Duan; Yijia Wei; Imran Ali; Jiang Huang; Jia Liang; Jianyong Hu; Jiazhi Zhang; Zixin Zhou (Algal Research, 2025)

Antioxidant and anti-inflammatory activities and action mechanisms of exopolysaccharides from Lactiplantibacillus plantarum Z-1 - Qiong Xu; Miao-Miao Wang; Xinyue Li; Ya-Rui Ding; Xiao-Yi Wei; Tao Zhou (Food Bioscience, 2024)

PABPN1 functions as a predictive biomarker in colorectal carcinoma - Qing-hua Wang; Pei-ci Yan; Li-zhou Shi; Ya-jie Teng; Xiao-jiao Gao; Li-qian Yao; Zhi-wei Liang; Ming-hui Zhou; Wei Han; Rui Li (Molecular Biology Reports, 2024)

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

The creation of multi-level urban ecological cooling network to alleviate the urban heat island effect - Yingying Li; Shumei Wang; Shujun Zhang; Min Wei; Yongsheng Chen; Xiaoyi Huang; Rui Zhou (Sustainable Cities and Society, 2024)

T cell senescence may contribute to immunothrombosis via Th17 immune transition in COVID-19 - Wenxing Li; Rui Qian; Zhaoming Zhou; Lei Wen; Quan Yin; Xiang Zhou; Xiaowei Li; Jie Cheng; Xinlu Zhang; Xin Zeng; Zhuoya Wang; Yingying Huang; et al. (Science Bulletin, 2024)

Preparation and properties of cationic starch-carrageenan‑sodium alginate hydrogels with pH and temperature sensitivity - Zheng Cai; Wei Zhou; Wenjing Chen; Rui Huang; Rui Zhang; Li Sheng; Miaomiao Shi; Yong Hu; Chao Huang; Yun Chen (Food Chemistry, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Phthalates on indoor surfaces and associated exposure via surface touch behavior: Observation in university dormitories and its implications - Fangzhou Yuan; Yu Sun; Na Li; Jianping Cao; Nan Zhang; Daniel Mmereki; Zhonghua Wei; Rui Chen; Jinyu Zhou; Yousheng Xu; Zhongming Bu (Building and Environment, 2024)

Olfactory perceptual interactions of maltol with key food odorants in binary mixtures: Scatter matrix statistical analysis of odor intensity in heterogeneous perceptual situation - Wei Guan; Runhu Xin; Miao Liang; Yuanhao Zhou; Rui Wang; Yuping Liu (Food Chemistry, 2024)

Fabrication and characterization of oxidized starch-xanthan gum composite nanoparticles with efficient emulsifying properties - Zheng Cai; Wei Zhou; Rui Zhang; Yuqi Tang; Kun Hu; Fangfang Wu; Chao Huang; Yong Hu; Tao Yang; Yun Chen (Food Chemistry, 2024)

Effects of soy protein on alleviating iron deficiency anemia in suckling rats with different iron supplements - Mengxiao Hu; Jun Zhou; Lili Qiu; Rui Song; Xiyu Qin; Zidi Tan; Wei Wang; Rong Liu; Yun Li; Yingyi Mao; Xiang Li; Fei Li; et al. (Food Bioscience, 2024)

Myo-inositol: A potential game-changer in preventing gill cell death and alleviating “gill rot” in grass carp (Ctenopharyngodon idellus) - Jie Chen; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Rui-Nan Zhang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

Dialdehyde starch cross-linked aminated gelatin sponges with excellent hemostatic performance and biocompatibility - Yu-He Zhu; Chen-Yu Zhou; Xu Peng; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Xiao-Jie Ju; Liang-Yin Chu (Carbohydrate Polymers, 2024)

DDLA: a double deep latent autoencoder for diabetic retinopathy diagnose based on continuous glucose sensors - Rui Tao; Hongru Li; Jingyi Lu; Youhe Huang; Yaxin Wang; Wei Lu; Xiaopeng Shao; Jian Zhou; Xia Yu (Medical & Biological Engineering & Computing, 2024)

Microbial Community Structure and Metabolism of Xinjiang Fine-Wool Sheep based on High-Throughput Sequencing Technology - Rui Yao; Fulin Li; Xuyang Dong; Yueren Xu; Ruirui Hu; Limin Wang; Kuojun Cai; Xiaogang Liu; Wei Ni; Ping Zhou; Shengwei Hu (Current Microbiology, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

The role of pantothenic acid in alleviating hypoxia-induced liver injury of sub-adult grass carp (Ctenopharyngodon idellus): Possible mechanisms and implication - Yan Xia; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Jia-Yong Tang; Rui-Nan Zhang; Lu Zhang; Hai-Feng Mi; Lin Feng (Aquaculture, 2024)

Hotspots lurking underwater: Insights into the contamination characteristics, environmental fates and impacts on biogeochemical cycling of microplastics in freshwater sediments - Haojie Chen; Danlian Huang; Wei Zhou; Rui Deng; Lingshi Yin; Ruihao Xiao; Sai Li; Fei Li; Yang Lei (Journal of Hazardous Materials, 2024)

Research progress of natural polysaccharide-based and natural protein-based hydrogels for bacteria-infected wound healing - Huiqing Xu; Yilin Che; Rui Zhou; Lu Wang; Jiaying Huang; Wei Kong; Chang Liu; Lei Guo; Yixin Tang; Xue Wang; Xi Yang; Erlei Wang; et al. (Chemical Engineering Journal, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Assessing environmental and human health risks: Insight from the enantioselective metabolism and degradation of fenpropidin - Rui Li; Yingying Wu; Nuanhui Wen; Wenjie Wei; Wei Zhao; Yanhong Li; Liangliang Zhou; Minghua Wang (Environmental Pollution, 2024)

Positive temperature coefficient material based on silicone rubber/ paraffin/ graphite/ carbon nanotubes for wearable thermal management devices - Jian-Min Hao; Yin-Fa Yang; Yi-Tao Shen; Rui Zhou; Wei Zhang; Hua Chen; Wen-Long Cheng (Chemical Engineering Journal, 2024)

Micronutrient perspective on COVID-19: Umbrella review and reanalysis of meta-analyses - Yafei Xie; Jianguo Xu; Dan Zhou; Mingyue Guo; Mengxiang Zhang; Ya Gao; Ming Liu; Jiyuan Shi; Kelu Yang; Qingyong Zheng; Liang Zhao; Yu Qin; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Molecular characterization, expression analysis and function identification of Pf_IL-12p35, Pf_IL-23p19 and Pf_IL-12p40 genes in yellow catfish (Pelteobagrus fulvidraco) - Xin-Xin Jiang; Zi-Rui Tang; Zhang-Ping Li; Gui-Rong Zhang; Xu Zhou; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2024)

Multi-source monitoring data filtering assisted deformation analysis model updating of ultra-high rockfill dam - Zhitao Ai; Gang Ma; Guike Zhang; Rui Liu; Shaohui Deng; Xiaolin Chang; Wei Zhou (Computers and Geotechnics, 2024)

Celastrol induced the autophagy of spermatogonia cells contributed to tripterygium glycosides-related testicular injury - Dong-Xiao Cui; Ze-Chen Niu; Xi Tang; Chun-Zhou Cai; Ding-Qiao Xu; Rui-Jia Fu; Wen-Juan Liu; Yu-Wei Wang; Yu-Ping Tang (Reproductive Toxicology, 2024)

Enhancing long-term river water quality prediction: Construction and validation of an improved hybrid model - Yadan Yu; Yangwu Chen; Shunbo Huang; Rui Wang; Houzhen Zhou; Chuankun Liu; Wei Wang; Zhouliang Tan (Process Safety and Environmental Protection, 2024)

Ammonium addition reduces phosphorus leaching in a long-term mineral or organic fertilized calcareous soil during flooding conditions - Lulu Wei; Yan Zhou; Guiming Yin; Jianyu Cui; Junhui Yin; Rui Liu; Qing Chen; Shuai Zhang (Journal of Environmental Management, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Soil moisture drives the shift from selection to complementarity effect in the rainfed maize/faba bean intercropping system - Wei Wang; Meng-Ying Li; Wei Zhang; Aziz Khan; Rui Zhou; Shuang-Guo Zhu; Bao-Zhong Wang; Yu-Miao Yang; Hong-Yan Tao; Wen-Bo Li; You-Cai Xiong (Plant and Soil, 2024)

An observational prospective study based on a large cohort of HIV-negative neurosyphilis patients with particular reference to the Jarisch-Herxheimer reaction - Rui-Rui Peng; Juan Wu; Wei Zhao; Lin Zhu; Zhifang Guan; Xin Gu; Mei Shi; Junjun Yu; Yanchun Cheng; Pingyu Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The purpose of this study is to outline a complete picture of Jarisch-Herxheimer reaction (JHR) in the central nervous system among HIV-negative neurosyphilis patients. Methods A prospective study cohort of 772 cases with almost all stages of neurosyphilis depicted the features of JHR including occurrence rate, risk profiles, clinical manifestations, medical management and prognosis. Results The total occurrence rate of JHR was 9.3% (95% CI, 7.3-11.4%), including 4.1% (95% CI, 2.7-5.6%) with severe JHR. The reaction started 5 h after treatment initiation, peaked after 8 h, and subsided after 18 h. Patients with severe JHR experienced a longer recovery time (26 h). Patients with general paresis (OR = 6.825), ocular syphilis (OR = 3.974), pleocytosis (OR = 2.426), or a high CSF-VDRL titre (per log 2 titre increase, OR = 2.235) were more likely to experience JHR. Patients with general paresis had an 11.759-fold increased risk of severe JHR. Worsening symptoms included cognitive impairment, mania, nonsense speech, and dysphoria, while symptoms of hallucination, urination disorder, seizures, myoclonus, or aphasia appeared as new-onset symptoms. Neurosyphilis treatment did not need to be interrupted in most patients with JHR and could be reinstated in patients with seizures under supportive medication when JHR subsided. Conclusion Severe JHR displayed a 4.1% occurrence rate and clinicians should pay particular attention to patients at a higher risk of JHR. The neurosyphilis treatment regime can be restarted under intensive observation for patients with severe JHR and, if necessary, supportive medication should be initiated and continued until the end of therapy.

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Domain generalization of chemical process fault diagnosis by maximizing domain feature distribution alignment - Kun Zhou; Rui Wang; Yifan Tong; Xiaoran Wei; Kai Song; Xu Chen (Process Safety and Environmental Protection, 2024)

ZnS-coated Yb3+-doped perovskite quantum dots: A stable and efficient quantum cutting photon energy converter for silicon-based electronics - Yue Wang; Nan Ding; Donglei Zhou; Wen Xu; Rui Sun; Wei Li; Yuqi Wang; Liheng Sun; Songtao Hu; Hongwei Song (Chemical Engineering Journal, 2024)

Generation of tau dephosphorylation-targeting chimeras for the treatment of Alzheimer’s disease and related tauopathies - Jingfen Su; Yue Xiao; Linyu Wei; Huiyang Lei; Fei Sun; Weixia Wang; Jun Yin; Rui Xiong; Shihong Li; Pei Zhang; Ying Zhou; Xiaochuan Wang; et al. (Science Bulletin, 2024)

Cadmium disrupts spermatogenic cell cycle via piRNA-DQ717867/p53 pathway - Jiaoyang Wei; Juan Dai; Xiaofan Shi; Ruixue Zhao; Guoqing Fu; Rui Li; Chao Xia; Ling Zhang; Ting Zhou; Huaiji Wang; Yuqin Shi (Reproductive Toxicology, 2024)

Retarding ice recrystallization by tamarind seed polysaccharide: Investigation in ice cream mixes and insights from molecular dynamics simulation - Xianbao Sun; Rui Guo; Taijie Zhan; Yuxing Kou; Xuan Ma; Hong Song; Wei Zhou; Lihua Song; Hui Zhang; Fan Xie; Chunmei Yuan; Zibo Song; et al. (Food Hydrocolloids, 2024)

Preparation and properties of pH-sensitive cationic starch nanoparticles - Wei Zhou; Rui Zhang; Zhen Cai; Fangfang Wu; Yong Hu; Chao Huang; Kun Hu; Yun Chen (Food Chemistry, 2024)

Water Properties and Diffusive Convection in the Canada Basin - Ling Qu; Shuangxi Guo; Shengqi Zhou; Yuanzheng Lu; Mingquan Zhu; Xianrong Cen; Di Li; Wei Zhou; Tao Xu; Miao Sun; Rui Zeng (Journal of Marine Science and Engineering, 2024)
The aim of this study is to better understand diffusive convection (DC) and its role in the upper ocean dynamic environment and sea ice melting in the Canada Basin. Based on a moored dataset with 6737 profiles collected from August 2003 to August 2011 in the upper layer of the Canada Basin, DC between the warm and salty Atlantic Water (AW) and the colder and less salty Lower Halocline Water (LHW) were investigated. The moorings were designated at four stations: A, B, C, and D, located at the southwestern, southeastern, northeastern, and northwestern parts of the basin, respectively. During the observation period, the temperature, salinity, and depth of the AW and LHW exhibited unique temporal variations. The temperature and salinity of the AW varied among stations, with a decreasing trend from northwest to southeast, consistent with the propagation path of the AW in the Canada Basin. The temperature and salinity of the LHW were similar at all stations. The AW and LHW cores were located between depths of 320–500 m and 160–300 m, respectively, and both gradually deepened over time. Distinct DC staircase structures were observed between the AW and LHW, more pronounced at stations C and D than at stations A and B, which is speculated to be related to eddies at stations A and B during the observation period. The vertical heat fluxes through the DC staircase layer at stations C and D (FHc_C and FHc_D) were estimated using an empirical formula. FHc_C ranged from 0.05 to 0.94 W/m2, and FHc_D ranged from 0.05 to 0.6 W/m2, with the maximum probability value for both at approximately 0.2 W/m2. The effective diffusivities at these two stations (KT_C and KT_D) are similar, ranging from 2 × 10−6 to 3 × 10−5 m2/s, with the highest probability occurring at 6 × 10−6 m2/s. Both the probability density function of the heat flux and the effective diffusivity skewed towards larger values and obey a lognormal distribution, indicating turbulence intermittency of the DC staircase in the Canada Basin. These finding offers new insights into the heat transport and turbulence in the DC staircase, and then bring a deeper understanding of sea ice melting in the Canada Basin.

Cycloaspeptide H, a cyclopentapeptide from the endophytic fungus Penicillium virgatum - Ben-Chao Li; Liu-Xia Lv; Li-Li Huang; Jia-Tong Zhou; Xi-Shan Huang; Jun Li; Rui-Yun Yang; Wei-Feng Xu (Natural Product Research, 2024)

High-density lipoprotein cholesterol is associated with lowered cognitive recovery among acute ischemic stroke patients with mild cognitive impairment - Rui Wang; Zhuomin Jiao; Anxin Wang; Yijun Zhang; Xiangxiang Hong; Shan Huang; Jin Fu; Yinglian Zhou; Yifei Wang; Chunyang Li; Yue Liu; Ke Wei; et al. (Acta Neurologica Belgica, 2024)

Advances, challenges, and prospects in microalgal-bacterial symbiosis system treating heavy metal wastewater - Xing-Rui Zhou; Rong Wang; Cong-Cong Tang; Cristiano Varrone; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Chemosphere, 2023)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

m6A modification associated with YTHDF1 is involved in Japanese encephalitis virus infection - Xiao-han Li; Jing Chen; Yu-da Ou; Xiang Zhong; Jia-huan Hu; Rui-cong Sun; Ying-jun Lv; Jian-chao Wei; Yun Young Go; Bin Zhou (Veterinary Microbiology, 2023)

Microbial mechanism of biochar addition to reduce N2O emissions from soilless substrate systems - Xiaofeng Liang; Wanlai Zhou; Rui Yang; Dongdong Zhang; Hong Wang; Qiaozhen Li; Zhiyong Qi; Yuzhong Li; Wei Lin (Journal of Environmental Management, 2023)

Exploring the relation between aggregation and adsorption of microplastics in aquatic environment containing metal cations - Weiqian Liang; Yingyue Zhou; Shuyin Wei; Longxia Lan; Jinfeng Chen; Jiawei Zhao; Hao Wang; Rui Gao; Feng Zeng (Journal of Environmental Chemical Engineering, 2023)

Mitochondrial dysfunction: a new molecular mechanism of intervertebral disc degeneration - Chao Song; Yulin Xu; Qinghua Peng; Rui Chen; Daqian Zhou; Kang Cheng; Weiye Cai; Tao Liu; Chenyi Huang; Zhijiang Fu; Cong Wei; Zongchao Liu (Inflammation Research, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Three Types of Enteromorpha prolifera Bio-Products Based on Different Processing Procedures as Feed Additives in the Diets of Pacific White Shrimp (Litopenaeus vannamei) - Zhibin Zhou; Lubo Wang; Mingqin Dai; Qingyan Gao; Peng Wang; Lili Zhao; Yanlu Li; Rui Xi; Mingchao Pan; Qiang Ma; Houguo Xu; Mengqing Liang; et al. (Fishes, 2023)
A feeding trial was conducted to evaluate the biological activities of Enteromorpha prolifera bio-products in the diets of Pacific white shrimp (Litopenaeus vannamei). Bio-products of E. prolifera included E. prolifera meal, E. prolifera hydrolysate and E. prolifera polysaccharide, which was supplied using different processing procedures. The control diet was supplemented without any E. prolifera bio-products or dietary attractants. Experimental diets were formulated to contain 0.2% and 0.4% of E. prolifera hydrolysate (EPH0.2% and EPH0.4%), 0.03% of E. prolifera polysaccharide (EPP0.03%), 3% of E. prolifera meal (EPM3%), 0.1% of dimethyl-β-propiothetn (DMPT0.1%) and 1% of squid paste (SP1%). Shrimp (~8 g) were randomly distributed in 21 tanks and fed for 44 days. Feed intake showed that 3% of E. prolifera meal and 0.4% of E. prolifera hydrolysate in diets exhibited similar attractant effects as 0.1% of DMPT. Gross qualitative observation showed that the abundance of lipid droplets decreased in hepatopancreas of the EPH0.4% and EPM3% groups, which were supported by hepatopancreas triacylglycerol (TG), where significantly lower concentrations were observed in the EPH0.4% and EPM3% groups compared with the control group. Similarly, TG and low-density lipoprotein cholesterol in serum significantly decreased in the EPH0.4%, EPP0.03% and EPM3% groups compared to the control group. Supplemental E. prolifera bio-products resulted in significantly higher serum glutathione level of EPP0.03% or superoxide dismutase activities of EPH0.4% and EPM3%, but significantly lower serum malondialdehyde level of EPM3%. In addition, tnf-α expression in hepatopancreas was significantly down-regulated in shrimp fed the EPH0.2%, EPH0.4% and EPM3% diets. Based on survival analysis, E. prolifera bio-products improved the resistance of shrimp to hypoxic stresses. Thus, this study confirmed that bio-products of E. prolifera supplied using different processing procedures could be used to reduce the amount of E. prolifera in feed of shrimp without compromising their biological functions.

New perspective into possible mechanism in growth promotion of potassium diformate (KDF) on the juvenile grass carp (Ctenopharyngodon idella) - Xue Xue; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Rui-Nan Zhang; Lin Feng (Aquaculture, 2023)

Recombinant Klotho alleviates vancomycin-induced acute kidney injury by upregulating anti-oxidative capacity via JAK2/STAT3/GPx3 axis - MengMeng Wang; Yue Zhou; GuoXiang Hao; Yue E. Wu; Rui Yin; Yi Zheng; Wei Zhao (Toxicology, 2023)

Synergetic effect on fouling alleviating of membrane distillation in urine resource recovery by thermally activated peroxydisulfate pretreatment - Yaping Lyu; Xiuwei Ao; Zongsu Wei; Shikun Cheng; Xiaoqin Zhou; Nana Liu; Xuemei Wang; Rui Feng; Zifu Li (Environmental Research, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Two new amides from the seeds of Coix lacryma-jobi var. lacryma-jobi - Xin Yin; Wei-qian Zhu; Yong-qiang Zhou; Rui-hang Hu; Xin Wei; Ting-ting Feng; Ying Zhou (Natural Product Research, 2023)

Large-scale biomonitoring of bisphenol analogues and their metabolites in human urine from Guangzhou, China: Implications for health risk assessment - Hao Wang; Rui Gao; Weiqian Liang; Shuyin Wei; Yingyue Zhou; Zhuo Wang; Longxia Lan; Jinfeng Chen; Feng Zeng (Chemosphere, 2023)

Application of enzymatically treated Artemisia annua L. on adult grass carp (Ctenopharyngodon idella): Improved growth performance, intestinal antioxidant capacity and apical junctional complex - Qin-Qin Dai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; He-Qun Shi; Lu Zhang; Hai-Feng Mi; Jia-Yong Tang; Rui-Nan Zhang; Lin Feng (Aquaculture, 2023)

Soil phosphorus availability mediates facilitation dynamic in maize-grass pea intercropping system - Shuang-Guo Zhu; Wesly Kiprotich; Zheng-Guo Cheng; Rui Zhou; Jing-Wei Fan; Hao Zhu; Wen-Ying Wang; Wei Wang; Ren-Qing Wang; Hong-Yan Tao; You-Cai Xiong (Soil and Tillage Research, 2023)

Effects of interspecific interactions on soil carbon emission and efficiency in the semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Shuang-Guo Zhu; Hong-Yan Tao; Aziz Khan; Aimee Grace Uzamurera; Bao-Zhong Wang; Jun-Ming Jin; Yue Ma; Wen-Bo Li; Xiu-Ping Tao; et al. (Soil and Tillage Research, 2023)

Rapid determination of the relative configuration of diverse 8,4′-oxyneolignans by NMR analysis: Retrospective studies, improvement and structural revision - Peng Zhao; Li-Li Lou; Ben-Song Xin; Zhi-Yuan Li; Rui Guo; Wei-Yu Zhou; Tian-Ming Lv; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Zero-valent cobalt and oxygen vacancy rich catalyst derived from Ni/Co metal-organic framework nanosheets for enhanced oxidation of aqueous contaminants via peroxymonosulfate activation - Haodong Hu; Xinlong Yan; Qingxun Hu; Xiaoyan Hu; Rui Feng; Tianbo Li; Wei Zhou; Liping Wang (Journal of Environmental Chemical Engineering, 2023)

Leaf senescence, nitrogen remobilization, and productivity of maize in two semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Fei Mo; Aziz Khan; Asfa Batool; Wei Zhang; Jun-Sheng Lu; Ying Zhu; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; et al. (European Journal of Agronomy, 2023)

A novel starch-based ethanol gel with contact-killing bacteria to cut off contact transmission of bacteria - Fu-Xiang Wei; Tian-Rui Zhou; Shao-Wei Zhong; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Chemical Engineering Journal, 2023)

Bradykinin-pretreated Human cardiac-specific c-kit+ Cells Enhance Exosomal miR-3059-5p and Promote Angiogenesis Against Hindlimb Ischemia in mice - Jingzhou Li; Fei Song; Ruolan Chen; Jinjuan Yang; Jie Liu; Li Huang; Fuyu Duan; Meng Kou; Boon Xuan Lian; Xiaoxia Zhou; Weimin Han; Liang Mao; et al. (Stem Cell Reviews and Reports, 2023)

Effects of Snail Bellamya purificata Farming at Different Stocking Densities on the Algal and Fungal Communities in Sediment - Yiran Hou; Mengmeng Zhou; Rui Jia; Wei Sun; Yanhong Yang; Xiongjian Huang; Bing Li; Jian Zhu (Fishes, 2023)
The snail Bellamya purificata is recognized as a potential bio-remediation species, and is commonly employed in polyculture to enhance resource utilization efficiency and realize culture environment regulation. In order to enrich the microbiome studies on elucidating the ecological effects of snail B. purificata farming, we assessed the effect of B. purificata farming activities, at varying stocking densities, on the algal and fungal communities in sediment. Four experimental groups were established in our study, each corresponding to a different stocking density: 0, 234.38, 468.75, and 937.5 g/m2, represented as CON, LD, MD, and HD, respectively. High-throughput sequencing based on ITS and 23S ribosomal RNA (rRNA) genes was employed to analyze the variations in algal and fungal communities under B. purificata farming activities at different stocking densities. B. purificata farming activities had no significant effect on the alpha diversities of fungal and algal communities, but significantly altered the compositions of fungal and algal communities in sediments, especially B. purificata farming activity at low stocking density. B. purificata farming activities at low stocking density could significantly increase the relative abundances of fungal genera Paraconiothyrium and Penicillium compared with the CON group. The promoting effect diminished with increasing density. B. purificata farming activities at low or medium stocking density also could enhance the relative abundances of algal genera Microchloropsis, Scenedesmus, and Auxenochlorella. Hence, B. purificata farming activity at low stocking density might be the optimum density to enhance resource utilization efficiency and minimize environmental pollution.

Identification of priority pollutants and key factors affecting environmental risks of lead‑zinc mine tailing sites - Jing-yu Peng; Shuai Zhang; Yu-jing Wang; Rui-feng Zhao; Yi-ling Zhou; Jian-wei Zhou (Science of The Total Environment, 2023)

Nitrate attenuation with rising groundwater levels: An integrated assessment using isotope tracers and microbial signatures - Jie Li; Yulian Liu; Wei Dai; Jian Li; Pingheng Yang; Lijun Tian; Shihang Yu; Rui Zuo; Yuanzheng Zhai; Wei Song; Fan Yang; Ruijing Zhou; et al. (Journal of Hydrology, 2023)

Preparation and emulsification properties of cationic starch-xanthan gum composite nanoparticles - Wei Zhou; Zhen Cai; Rui Zhang; Kun Hu; Fangfang Wu; Yong Hu; Chao Huang; Yun Chen (Food Chemistry, 2023)

Antimicrobial hydrogel microneedle loading verteporfin promotes skin regeneration by blocking mechanotransduction signaling - Chengxiu Wei; Chuangang You; Liming Zhou; Huiling Liu; Shihao Zhou; Xingang Wang; Rui Guo (Chemical Engineering Journal, 2023)

Numeric and nonnumeric information input to predict adsorption amount, capacity and kinetics of tetracyclines by biochar via machine learning - Bai-Qin Zhou; Rui-Chun Yang; Hui-Ping LI; Yu-Jun Wang; Chun-Yue Zhang; Zi-Jie Xiao; Zhong-Qi He; Wei-Hai Pang (Chemical Engineering Journal, 2023)

A new oleanane-type triterpene from Ardisia lindleyana D.Dietr and its cytotoxic activity - Zhou Tiqiang; Wei Zhenzhen; Fu Qianyu; Qiu Rui; Zhang Guangjie; Li Bin; Dong Junxing; Zeng Chengchu (Natural Product Research, 2023)

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

Highly stretchable phase change composites for simultaneous health monitoring and thermotherapy - Yi-Cun Zhou; Jie Yang; Wu-Di Li; Peng Yu; Zheng-Min Zhang; Lu Bai; Rui-Ying Bao; Wei Yang (Chemical Engineering Journal, 2023)

Star-like, dopant-free, corannulene-cored hole transporting materials for efficient inverted perovskite solar cells - Ming-Wei An; Bolin Li; Bin-Wen Chen; Zuo-Chang Chen; Han-Rui Tian; Lin-Long Deng; Xugang Guo; Zhou Xing (Chemical Engineering Journal, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Pathogenicity characteristics of the entomopathogenic fungus Cordyceps javanica IJ-tg19 to Acyrthosiphon pisum - Di Wang; Pei-Xiang Xing; Hong-Liang Diao; Wen-Wen Zhou; Xian-Wei Li; Li-Jun Zhang; Rui-Yan Ma (BioControl, 2023)

Selective CDK9 knockdown sensitizes TRAIL response by suppression of antiapoptotic factors and NF-kappaB pathway - Qian Yuan; Kui Su; Shuyi Li; Xinyi Long; Lang Liu; Jianwu Sun; Xin Yuan; Minghui Yang; Rui Tian; Wanting Zhang; Zhujie Deng; Quanjiang Li; et al. (Apoptosis, 2023)

Thickness effects of polyethylene and biodegradable film residuals on soil properties and dryland maize productivity - Aimee Grace Uzamurera; Ze-Ying Zhao; Peng-Yang Wang; Yong-Xian Wei; Fei Mo; Rui Zhou; Wen-Li Wang; Fazal Ullah; Aziz Khan; Xiao-Bin Xiong; Meng-Ying Li; Kiprotich Wesly; et al. (Chemosphere, 2023)

Nanostructured carboxylated-wood aerogel membrane for high-efficiency removal of Cu (II) ions from wastewater - Wen He; Jizhou Cao; Feiyu Guo; Zhihao Guo; Peiguo Zhou; Rui Wang; Shuang Liang; Qunyan Pang; Bairen Wei; Yue Jiao; Tripti Singh; Qiliang Fu (Chemical Engineering Journal, 2023)

Novel insights into tumorigenesis and prognosis of endometrial cancer through systematic investigation and validation on mitophagy-related signature - Rui Sun; Xiaoyu Zhou; Tong Wang; Yao Liu; Lina Wei; Ziyi Qiu; Chunping Qiu; Jie Jiang (Human Cell, 2023)

Enhanced nitrate reduction by metal deposited g-C3N4/rGO/TiO2 Z-schematic photocatalysts: Performance and mechanism comparison of Pd-Cu and Ag - Houfen Li; Shuai Xue; Fang Cao; Cong Gao; Qian Wei; Rui Li; Aijuan Zhou; Sufang Wang; Xiuping Yue (Chemosphere, 2023)

Colletotrins A-C, three new sesquiterpenes from the endophytic fungus Colletotrichum iris strain S11 - Ning Chen; Shi-Yu Qiu; Song-Mei Lu; Shi-Wei Chen; Ji-Rui Wei; Fu-Wen Yang; Hui-Chun Geng; Min Zhou (Phytochemistry Letters, 2023)

Can shallow-incorporated organic mulching replace plastic film mulching for irrigated maize production systems in arid environments? - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Rui Zhou; Ying Zhu; Yi-Bo Wang; Ning Wang; Kiprotich Wesly; Wei Xue; Jing Cao; Jin-Lin Zhang; Hong-Yan Tao; et al. (Field Crops Research, 2023)

A deep learning nomogram of continuous glucose monitoring data for the risk prediction of diabetic retinopathy in type 2 diabetes - Rui Tao; Xia Yu; Jingyi Lu; Yaxin Wang; Wei Lu; Zhanhu Zhang; Hongru Li; Jian Zhou (Physical and Engineering Sciences in Medicine, 2023)

Large-scale characteristics of thermokarst lakes across the source area of the Yellow River on the Qinghai-Tibetan Plateau - Wen-hui Liu; Guang-hao Zhou; Hai-rui Liu; Qing-peng Li; Chang-wei Xie; Qing Li; Jian-yun Zhao; Qi Zhang (Journal of Mountain Science, 2023)

A review of the development in shale oil and gas wastewater desalination - Simin Zhou; Likun Huang; Guangzhi Wang; Wei Wang; Rui Zhao; Xiyu Sun; Dongdong Wang (Science of The Total Environment, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A20 ameliorates disc degeneration by suppressing mTOR/BNIP3 axis-mediated mitophagy - Xin Peng; Cong Zhang; Jia-Wei Gao; Feng Wang; Jun-Ping Bao; Zhi-Min Zhou; Rui Sun; Hang-Yu Ji; Cabral VLF; Xiao-Tao Wu (Genes & Genomics, 2023)

Evaluation method of rowing performance and its optimization for UAV-based shot seeding device on rice sowing - Wei Liu; Zhiyan Zhou; Xuelang Xu; Qingyu Gu; Shuaishuai Zou; Weizhuo He; Xiwen Luo; Junhao Huang; Jianqin Lin; Rui Jiang (Computers and Electronics in Agriculture, 2023)

An ultra-thin chemical vapor deposited polymer interlayer to achieve highly improved stability of perovskite solar cell - Jing Zhou; Xueying Tian; Rui Chen; Weitao Chen; Xin Meng; Xinyu Guan; Jianan Wang; Sanwan Liu; Fumeng Ren; Shasha Zhang; Yiqiang Zhang; Zonghao Liu; et al. (Chemical Engineering Journal, 2023)

Creation of intermuscular bone-free mutants in amphitriploid gibel carp by editing two duplicated runx2b homeologs - Rui-Hai Gan; Zhi Li; Zhong-Wei Wang; Xi-Yin Li; Yang Wang; Xiao-Juan Zhang; Jin-Feng Tong; Yue Wu; Ling-Yun Xia; Ze-Xia Gao; Li Zhou; Jian-Fang Gui (Aquaculture, 2023)

Effects of vacuum drying assisted with condensation on drying characteristics and quality of apple slices - Xin Bao; Rui Min; Kai Zhou; Maria Victoria Traffano-Schiffo; Quan Dong; Wei Luo (Journal of Food Engineering, 2023)

Combine thermal processing with polyvalent phage LPEK22 to prevent the Escherichia coli and Salmonella enterica contamination in food - Yue Zhang; Geng Zou; Md. Sharifull Islam; Kun Liu; Suqiang Xue; Zhiyong Song; Yingwang Ye; Yang Zhou; Yuanguo Shi; Shaozhong Wei; Rui Zhou; Huanchun Chen; et al. (Food Research International, 2023)

Highly sensitive surface-enhanced Raman scattering (SERS) imaging for phenotypic diagnosis and therapeutic evaluation of breast cancer - Chonggui Qiu; Wei Zhang; Yanhong Zhou; Hongwang Cui; Yanlong Xing; Fabiao Yu; Rui Wang (Chemical Engineering Journal, 2023)

Changes in PM2.5-related health burden in China's poverty and non-poverty areas during 2000–2020: A health inequality perspective - Yan Li; Baojie Li; Hong Liao; Bing-Bing Zhou; Jing Wei; Yuxia Wang; Yuzhu Zang; Yang Yang; Rui Liu; Xiaorui Wang (Science of The Total Environment, 2023)

Self-assembly of Au nanocrystals into large-area 3-D ordered flexible superlattice nanostructures arrays for ultrasensitive trace multi-hazard detection - Wei Liu; Qian Li; Jiabin Wu; Weizhe Wang; Rui Jiang; Chunli Zhou; Shuangbao Wang; Xueming Zhang; Tangyou Sun; Zhimou Xu; Dingsheng Wang (Journal of Hazardous Materials, 2023)

Fabricated noble-metal free Co2B/g-C3N4 photocatalyst with 2D/2D structure achieved remarkable water splitting performance from visible to near-infrared wavelengths - Jun-ying Tang; Rui-tang Guo; Wei-guo Pan; Wei-guo Zhou (Fuel, 2023)

Effects of bepridil on early cardiac development of zebrafish - Ya-Lan Wei; Yu-Qing Lei; Zhou-Jie Ye; Xu-Dong Zhuang; Li-Ping Zhu; Xin-Rui Wang; Hua Cao (Cell and Tissue Research, 2023)

Intercrop overyielding weakened by high inputs: Global meta-analysis with experimental validation - Shuang-Guo Zhu; Hao Zhu; Rui Zhou; Wei Zhang; Wei Wang; Yi-Ning Zhou; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; Hong-Yan Tao; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

The Impacts of Dietary Curcumin on Innate Immune Responses and Antioxidant Status in Greater Amberjack (Seriola dumerili) under Ammonia Stress - Chuanpeng Zhou; Zhong Huang; Shengjie Zhou; Jing Hu; Rui Yang; Jun Wang; Yun Wang; Wei Yu; Heizhao Lin; Zhenhua Ma (Journal of Marine Science and Engineering, 2023)
In this study, we investigated the effect of dietary curcumin on non-specific immune responses and antioxidative ability in Seriola dumerili under ammonia stress and post-recovery. Three diets were prepared to contain 0, 75, and 150 mg/kg of curcumin. A total of 225 greater amberjack (initial weight: 100.90 ± 0.03 g) were distributed into nine cylindrical tanks, constituting an experimental design with three treatments and three replicates. After 56 days of feeding, plasma, intestinal, and hepatic enzyme activities were evaluated. Then, an acute ammonia challenge experiment was conducted. Ten fish per tank were subjected to acute ammonia stress (total ammonia-N: 1000 mg/L) for eight minutes followed by six minutes of recovery. The results indicated that dietary curcumin significantly promoted intestinal and hepatic alkaline phosphatase (ALP) and acid phosphatase (ACP) levels as well as hepatic antioxidative enzymes such as superoxide dismutase (SOD), total antioxidant capacity (T-AOC), reduced glutathione (GSH), and glutathione peroxidase (GSH-Px) of greater amberjack. In addition, curcumin addition improved the activities of antioxidant enzymes, such as SOD, T-AOC, GSH, GSH-Px, and catalase (CAT), and reduced malondialdehyde (MDA) content in liver, spleen, head kidney, and brain tissues after post-recovery. The indexes related to immunity and antioxidant enzymes in the liver, gill, and spleen rose again to some extent, but they showed the worst recovery ability in the head kidney and brain tissue samples. These results indicate that dietary curcumin supplementation could increase non-specific immune responses, antioxidant ability, and enhance resistance to high ammonia stress in juvenile S. dumerili.

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Binary Adsorption and Migration Simulation of Levofloxacin with zinc at Concentrations Simulating Wastewater on Silty Clay and The Potential Environmental Risk in Groundwater - Mengxian Wei; Xueshuang Wang; Kai Zhou; Rui Yang (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Insights into production and consumption processes of nitrous oxide emitted from soilless culture systems by dual isotopocule plot and functional genes - Wei Lin; QiaoZhen Li; Wanlai Zhou; Rui Yang; Dongdong Zhang; Hong Wang; Yujia Li; Zhiyong Qi; Yuzhong Li (Science of The Total Environment, 2023)

The constitutive behavior and dissociation effect of hydrate-bearing sediment within a granular thermodynamic framework - Bing Bai; Rui Zhou; Guangchang Yang; Weilie Zou; Wei Yuan (Ocean Engineering, 2023)

Characteristics of non-point source pollution based on monitoring experiment in the Yingwugou small watershed, China - Kai Peng; Jia-ke Li; Gai-rui Hao; Yi-wen Liu; Xiang Zhou; Wei-feng Xie (Ecohydrology & Hydrobiology, 2023)

Soil water and phosphorus availability determines plant-plant facilitation in maize-grass pea intercropping system - Shuang-Guo Zhu; Hao Zhu; Zheng-Guo Cheng; Rui Zhou; Yu-Miao Yang; Jing Wang; Wei Wang; Bao-Zhong Wang; Hong-Yan Tao; You-Cai Xiong (Plant and Soil, 2023)

The structure and subduction relicts of the Changchun–Yanji suture, NE China: new evidence from deep seismic reflection profiling - Jiaduo Zhang; Hesheng Hou; Jianbo Zhou; Wei Fu; Rui Guo; Zongdong Pan; Hengcheng Ying (International Journal of Earth Sciences, 2022)

The inhibition of CFTR in the descended testis of SD rats with unilateral cryptorchidism induced by di-(2-ethylhexyl) phthalate (DEHP) - Xiangliang Tang; Dian Li; Tianxin Zhao; Shibo Zhu; Xiaofeng Gao; Rui Zhou; Fuming Deng; Wen Fu; Wei Jia; Guochang Liu (Environmental Science and Pollution Research, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

A New Framework Based on Data-Based Mechanistic Model and Forgetting Mechanism for Flood Forecast - Guozhen Wei; Wei Ding; Guohua Liang; Bin He; Jian Wu; Rui Zhang; Huicheng Zhou (Water Resources Management, 2022)

Activation of the TREK-1 Potassium Channel Improved Cognitive Deficits in a Mouse Model of Alzheimer’s Disease by Modulating Glutamate Metabolism - Fang Li; Shu-ning Zhou; Xin Zeng; Zhen Li; Rui Yang; Xue-xi Wang; Bin Meng; Wei-lin Pei; Li Lu (Molecular Neurobiology, 2022)

Long non‑coding RNA PART1: dual role in cancer - Rui Ran; Chao-Yang Gong; Zhi-Qiang Wang; Wen-Ming Zhou; Shun-Bai Zhang; Yong-Qiang Shi; Chun-Wei Ma; Hai-Hong Zhang (Human Cell, 2022)

Hydrochemical Evolution and Nitrogen Behaviors in Coastal Groundwater Suffered From Seawater Intrusion and Anthropogenic Inputs - Yu Dun; Junhong Ling; Rui Wang; Jun Wei; Qianyi Zhou; Yingjie Cao; Yizhang Zhang; Yingxue Xuan (Frontiers in Marine Science, 2022)
Coastal aquifers play key roles in providing freshwater resources to maintain the social and economic development in coastal areas. However, climate change and human activities have dramatically affected the quantities and qualities of groundwater in coastal aquifers. In this study, stoichiometric analysis of hydrogeochemistry, multivariate analysis, and isotopic trancing techniques were used to reveal the local hydrochemistry characteristics, the natural and anthropogenic origins, and the major hydrochemical evolution in a typical coastal aquifer located in the Pearl River estuary. According to hydrogeological conditions and groundwater burial conditions, the aquifer was divided into three zones, namely, semiconfined fissure groundwater (SFGW), recharged fissure groundwater (RFGW), and porous medium groundwater (PGW). Seawater intrusion, ion exchange, water–rock reaction, and human activities were the main controlling factors affecting the characteristics of groundwater, but there were significant differences in the main controlling effects of different zones. Among them, the samples from the SFGW was severely affected by seawater intrusion, and the contributions of seawater ranged from 6% to 97%. Obvious cation exchange process occurred during the seawater intrusion. The hydrochemical characteristics of the PGW and the RFGW were mainly controlled by water–rock interaction. In addition, human activities had further influence on the hydrochemical characteristics of groundwater, which resulted in elevated nitrate–nitrogen (NO 3 − –N). The mean NO 3 –N concentrations in the PGW and the SFGW were 6.58 and 3.07 mg/L, respectively. Furthermore, the δ 15 N–NO 3 − and δ 18 O–NO 3 − values in these two regions ranged from +2.35‰ to +27.54‰ and from +0.39‰ to +18.95‰, respectively, indicating that the anthropogenic input contributed to the increased nitrate. Redox analysis and dual nitrogen isotopic evidence indicated that denitrification was the predominant biogeochemical process in the PGW and the RFGW. This study highlights the impacts of seawater intrusion and anthropogenic inputs on hydrochemical evolution and nitrogen behaviors in coastal groundwater, which provides a scientific basis for the management of groundwater resources in coastal aquifers.

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Cardiac Expression of Esophageal Cancer-Related Gene-4 is Regulated by Sp1 and is a Potential Early Target of Doxorubicin-Induced Cardiotoxicity - Dandan Long; Chunyue Chen; Wei Li; Wanling Peng; Dongmei Li; Rui Zhou; Xitong Dang (Cardiovascular Toxicology, 2022)

Regulation of Social Memory by Lateral Entorhinal Cortical Projection to Dorsal Hippocampal CA2 - Rui Dang; Yu Zhou; Yue Zhang; Die Liu; Miao Wu; An Liu; Zhengping Jia; Wei Xie (Neuroscience Bulletin, 2022)

SSR analysis and fingerprint construction to evaluate the genetic diversity of medicinal plum varieties - Rui Wang; Xin Li; Wei Zhang; Jinmei Ou; Chengwu Fang; Qianqian Song; Huiyin Zhou (Journal of Plant Biochemistry and Biotechnology, 2022)

Triculata A, a novel compound from Tricyrtis maculata (D. Don) J. F. Macbr. with biological properties - Li Ren; Yun-Ze Wang; Wei Zhang; Rui Zhou; Ming Zhao; Zhi-Shu Tang; Jing Sun; Dong-Bo Zhang (Natural Product Research, 2021)

Globular adiponectin inhibits osteoblastic differentiation of vascular smooth muscle cells through the PI3K/AKT and Wnt/β-catenin pathway - Yun Zhou; Li-Long Wei; Rui-Ping Zhang; Cheng-Wu Han; Yongtong Cao (Journal of Molecular Histology, 2021)
Lipid metabolism is closely related to the improvement of vascular calcification (VC) in chronic kidney disease (CKD). Globular adiponectin (gAd) has been reported to be involved in the development of VC in CKD, but the detailed regulatory role remains unclear. The present study is aimed to investigate the biological function and the underlying regulation mechanism of gAd in the process of VC during CKD. Vascular smooth muscle cells (VSMCs) calcification was determined by Alizarin Red S staining. Protein signaling related with VC was tested by western blotting. The expression and intracellular localization of runt-related transcription factor 2 (Runx2) was detected by immunofluorescence and uraemic rat with VC was established by a two-step nephrectomy. Combined with the results of Alizarin Red S staining, we discovered that β-glycerophosphate (β-Gp)-induced the osteoblastic differentiation of VSMCs was significantly reversed by gAd treatment. Along with the VSMCs calcification and the increase of Runx2 in β-Gp-exposed VSMCs, the activities of protein kinase B (AKT) and Wnt/β-catenin pathway were enhanced, but that were counteracted by the exposure of gAd in rat and human VSMCs. After administration with agonists of the Wnt (SKL2001) and AKT (SC79), there appeared more osteoblastic differentiation and higher expression of Runx2 in gAd-treated VSMCs, but showing lower impact in the presence of SC79 than that in the presence of SKL2001. In the in vivo experiments, intravenous injection of gAd also significantly inhibited VC and Runx2 level in uraemic rat in a dose-dependent manner, possibly through regulating Wnt/β-catenin pathway. This study demonstrates that gAd ameliorates osteoblastic differentiation of VSMCs possibly by blocking PI3K/AKT and Wnt/β-catenin signaling transduction. The findings provide an important foundation for gAd in treating VC in kidney diseases.

The Water Resisting Properties of the Top Portion of the Ordovician Limestone Aquifer in the North China Coalfield - Hao Wang; Shuning Dong; Rui Chai; Wei Qiao; Jian Yang; Ji Liu; Linsheng Zhou; Zhenfang Zhou; Zhaoxing Liu; Hongbo Shang (Mine Water and the Environment, 2021)

Heterogeneity of tight sandstone reservoirs based on fractal theory: the Xu-6 member of Xujiahe Formation in Guang'an area, central Sichuan Basin - Fang Shen; Liang Yue; Ziliang Liu; Wei Yang; Kaarel Mänd; Hui Jin; Fengjie Li; Yue Zhou; Minghe Zhang; Rui Jiang (Arabian Journal of Geosciences, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Astrocyte-Derived Lactate Modulates the Passive Coping Response to Behavioral Challenge in Male Mice - Ya-Nan Yin; Jian Hu; Yi-Li Wei; Ze-Lin Li; Zhou-Cai Luo; Rui-Qi Wang; Ke-Xin Yang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

Vallicoccus soli gen. nov., sp. nov., a novel actinobacterium isolated from soil, and description of Vallicoccaceae fam. nov., Motilibacterales ord. nov. - Yu-Zhou Feng; Wei-Xun Chunyu; Rui Liang; Richard L. Hahnke; Peter Schumann; Yu-Rong Zhao; Sheng Gao; Min Yin; Yang Ji; Le Sun; Xiao-Yang Zhi; Shu-Kun Tang (Antonie van Leeuwenhoek, 2020)

CD49a+CD49b+ NK cells induced by viral infection reflect an activated state of conventional NK cells - Wenhan Li; Jing Zhou; Xianwei Wang; Yuzhang Wu; Lilin Ye; Haiming Wei; Rui Sun; Zhigang Tian; Hui Peng (Science China Life Sciences, 2020)

The Forms, Distribution, and Risk Assessment of Sulfonamide Antibiotics in the Manure–Soil–Vegetable System of Feedlot Livestock - Caixia Jin; Shan Wei; Ruilian Sun; Wei Zou; Xingli Zhang; Qixing Zhou; Rui Liu; Liuqun Huang (Bulletin of Environmental Contamination and Toxicology, 2020)

Sulfur isotope and trace element compositions of pyrite determined by NanoSIMS and LA-ICP-MS: new constraints on the genesis of the Shuiyindong Carlin-like gold deposit in SW China - Jin-xiang Li; Rui-zhong Hu; Cheng-hai Zhao; Jing-jing Zhu; Yong Huang; Wei Gao; Jin-wei Li; Yu-zhou Zhuo (Mineralium Deposita, 2020)

Evolution of Neolithic site distribution (9.0–4.0 ka BP) in Anhui, East China - Li Wu; Xiaoling Sun; Wei Sun; Cheng Zhu; Tongxin Zhu; Shuguang Lu; Hui Zhou; Qingchun Guo; Houchun Guan; Wei Xie; Rui Ke; Guiping Lin (Journal of Geographical Sciences, 2020)

Experimental and numerical study on the load and deformation mechanism of a flexible net barrier under debris flow impact - Rui Jiang; Wen-ping Fei; Hong-wei Zhou; Miao Huo; Jia-wen Zhou; Jia-mei Wang; Jia-jun Wu (Bulletin of Engineering Geology and the Environment, 2020)

Quality dependence of litter decomposition and its carbon, nitrogen and phosphorus release under simulated acid rain treatments - Hui Wei; Rui Ma; Jiaen Zhang; Leyi Zhou; Ziqiang Liu; Zhenyi Fan; Jiayue Yang; Xiaoran Shan; Huimin Xiang (Environmental Science and Pollution Research, 2020)

In vitro and in vivo evaluation of the antifungal activity of fluoxetine combined with antifungals against Candida albicans biofilms and oral candidiasis - Liuliu Jiang; Linxia Zheng; K airui Sun; Peng Zhou; Rui Xu; Jingyi Gu; Xin Wei (Biofouling, 2020)

Development of 19 novel microsatellite markers of lily-of-the-valley (Convallaria, Asparagaceae) from transcriptome sequencing - Qi-Xiang Lu; Jing Gao; Jun-Jie Wu; Xuan Zhou; Xue Wu; Meng-Di Li; Yu-Kun Wei; Rui-Hong Wang; Zhe-Chen Qi; Pan Li (Molecular Biology Reports, 2020)

Sources and ore-forming fluid pathways of carbonate-hosted Pb–Zn deposits in Southwest China: implications of Pb–Zn–S–Cd isotopic compositions - Chong Xu; Hong Zhong; Rui-Zhong Hu; Han-Jie Wen; Wei-Guang Zhu; Zhong-Jie Bai; Hai-Feng Fan; Fang-Fang Li; Ting Zhou (Mineralium Deposita, 2020)

Characterization and fine mapping of Arabidopsis RLL3, a locus required for DNA demethylation pathway - Wei Miao; Jie Dai; Yumei La; Chong Lu; Jianzhen Zhang; Xinyue Hong; Shaoxia Zhou; Qianqian Wang; Xiangyu Wang; Qi Rui; Feng Tan; Honggui La (Molecular Genetics and Genomics, 2020)

Integrated analysis of miRNAs and their targets reveals that miR319c/TCP2 regulates apical bud burst in tea plant (Camellia sinensis) - Shengrui Liu; Xiaozeng Mi; Ran Zhang; Yanlin An; Qiying Zhou; Tianyuan Yang; Xiaobo Xia; Rui Guo; Xuewen Wang; Chaoling Wei (Planta, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Ginsenoside compound-K inhibits the activity of B cells through inducing IgD-B cell receptor endocytosis in mice with collagen-induced arthritis - Mei Zhang; Shanshan Hu; Juan Tao; Weijie Zhou; Rui Wang; Yu Tai; Feng Xiao; Qingtong Wang; Wei Wei (Inflammopharmacology, 2019)

The role of MAPK signaling pathway in formation of EMT in oral squamous carcinoma cells induced by TNF-α - Xiao-Wei Zhao; Jing-Ping Zhou; Yu-Lan Bi; Jia-Ying Wang; Rui Yu; Chao Deng; Wei-Kang Wang; Xian-Zhen Li; Rui Huang; Jili Zhang; De-Tao Tao (Molecular Biology Reports, 2019)

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

Dietary exposure to cadmium of Shenzhen adult residents from a total diet study - Zhou Wang; Liubo Pan; Guihua Liu; Huimin Zhang; Jinzhou Zhang; Jie Jiang; Ying Xiao; Weibin Bai; Rui Jiao; Wei Huang (Food Additives & Contaminants: Part A, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Estimating cadmium concentration in the edible part of Capsicum annuum using hyperspectral models - Ting Wang; Hong Wei; Cui Zhou; Yanwen Gu; Rui Li; Hongchun Chen; Wenchao Ma (Environmental Monitoring and Assessment, 2017)

Involvement of FMRP in Primary MicroRNA Processing via Enhancing Drosha Translation - Rui-Ping Wan; Lin-Tao Zhou; Hai-Xuan Yang; Yong-Ting Zhou; Shun-Hua Ye; Qi-Hua Zhao; Mei-Mei Gao; Wei-Ping Liao; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Inhibition of mTOR Pathway by Rapamycin Decreases P-glycoprotein Expression and Spontaneous Seizures in Pharmacoresistant Epilepsy - Xiaosa Chi; Cheng Huang; Rui Li; Wei Wang; Mengqian Wu; Jinmei Li; Dong Zhou (Journal of Molecular Neuroscience, 2017)

Thermal effects on development and adult longevity of endoparasitoid Chelonus murakatae Munakata (Hymenoptera: Braconidae) - Sundas Rana Qureshi; Wei-Li Quan; Rui-Qi Zhou; Fen Zhu; Xiao-Ping Wang (Environmental Science and Pollution Research, 2017)

MicroRNA-9 Mediates the Cell Apoptosis by Targeting Bcl2l11 in Ischemic Stroke - Na Wei; Lin Xiao; Rui Xue; Dandan Zhang; Jun Zhou; Huayan Ren; Si Guo; Jingjing Xu (Molecular Neurobiology, 2016)

Developmental and physiological properties of Pyropia dentata (Bangiales, Rhodophyta) conchocelis in culture - Zhi-hai Zhong; Wen-jun Wang; Xiu-tao Sun; Fu-li Liu; Zhou-rui Liang; Fei-jiu Wang; Wei-zhou Chen (Journal of Applied Phycology, 2016)

Suppressing Receptor-Interacting Protein 140: a New Sight for Salidroside to Treat Cerebral Ischemia - Tong Chen; Zhanqiang Ma; Lingpeng Zhu; Wenjiao Jiang; Tingting Wei; Rui Zhou; Fen Luo; Kai Zhang; Qiang Fu; Chunhua Ma; Tianhua Yan (Molecular Neurobiology, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Cloning and characterizing of the murine IRF-3 gene promoter region - Hua-Guo Xu; Lifei Liu; Shan Gao; Rui Jin; Wei Ren; Guo-Ping Zhou (Immunologic Research, 2016)

Two new triterpenoid glycosides from the stems of Camellia oleifera Abel - Qing-Wei Yan; Hui-Zheng Fu; Yue-Hua Luo; Guo-Ping Zhou; Kai-Hua Wan; Rui-Jian Zhong (Natural Product Research, 2016)

Dietary exposure to lead of adults in Shenzhen city, China - Liubo Pan; Zhou Wang; Zhaoqiong Peng; Guihua Liu; Huimin Zhang; Jinzhou Zhang; Jie Jiang; Nimal Pathiraja; Ying Xiao; Rui Jiao; Wei Huang (Food Additives & Contaminants: Part A, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Determinants of the biodiversity patterns of ammonia-oxidizing archaea community in two contrasting forest stands - Jie Chen; Yichao Rui; Xuan Zhou; Wanhui Ye; Wei Liu (Journal of Soils and Sediments, 2016)

ZmDBF3, a Novel Transcription Factor from Maize (Zea mays L.), Is Involved in Multiple Abiotic Stress Tolerance - Wei Zhou; Cheng-Guo Jia; Xian Wu; Rui-Xue Hu; Gang Yu; Xiang-Hui Zhang; Jin-Liang Liu; Hong-Yu Pan (Plant Molecular Biology Reporter, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

α7nAChR is expressed in satellite cells at different myogenic status during skeletal muscle wound healing in rats - Zhi-Ling Tian; Shu-Kun Jiang; Miao Zhang; Meng Wang; Jiao-Yong Li; Rui Zhao; Lin-Lin Wang; Min Liu; Shan-Shan Li; Meng-Zhou Zhang; Da-Wei Guan (Journal of Molecular Histology, 2015)

Distribution of the Vrn-D1b allele associated with facultative growth habit in Chinese wheat accessions - Xian-rui Guo; Yuan-yuan Wang; Ling-zhi Meng; Hong-wei Liu; Li Yang; Yang Zhou; Hong-jun Zhang (Euphytica, 2015)

The cardioprotective effect of salidroside against myocardial ischemia reperfusion injury in rats by inhibiting apoptosis and inflammation - Lingpeng Zhu; Tingting Wei; Jin Gao; Xiayun Chang; He He; Fen Luo; Rui Zhou; Chunhua Ma; Yu Liu; Tianhua Yan (Apoptosis, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

All-trans retinoic acid up-regulates the human CD2AP gene expression through Sp1/Sp3 binding sites - Hua-Guo Xu; Rui Jin; Shan Gao; Wei Ren; Li Zou; Lifei Liu; Guo-Ping Zhou (Immunologic Research, 2015)

Effects of Lettuce Glycoside B in Ameliorating Pulmonary Fibrosis Induced by Irradiation Exposure and its Anti-Oxidative Stress Mechanism - Yan Zhou; Yuan Gao; Yingying Chen; Rui Zheng; Wei Zhang; Mingqi Tan (Cell Biochemistry and Biophysics, 2015)

The role of visfatin on the regulation of inflammation and apoptosis in the spleen of LPS-treated rats - Ke Xiao; Wei-Hua Zou; Zhi Yang; Zia ur Rehman; Abdur Rahman Ansari; Huai-Rui Yuan; Ying Zhou; Lu Cui; Ke-Mei Peng; Hui Song (Cell and Tissue Research, 2015)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

Gabapentin Enhances the Morphine Anti-Nociceptive Effect in Neuropathic Pain via the Interleukin-10-Heme Oxygenase-1 Signalling Pathway in Rats - Yu-Hua Bao; Quan-Hong Zhou; Rui Chen; Hao Xu; Lu-Lu Zeng; Xin Zhang; Wei Jiang; Dong-Ping Du (Journal of Molecular Neuroscience, 2014)

Molecular cloning and expression analysis of mannose receptor in blunt snout bream (Megalobrama amblycephala) - Xiaoling Liu; Xiaocheng Tang; Li Wang; Jie Li; Hong Wang; Shun Wei; Rui Fang; Wei Ji; Gailing Yuan; Nan Chen; Zemao Gu; Xueqin Liu; et al. (Molecular Biology Reports, 2014)

Construction, characterization and expression of full length cDNA clone of sheep YAP1 gene - Wei Sun; Da Li; Rui Su; Hassan H. Musa; Ling Chen; Hong Zhou (Molecular Biology Reports, 2014)

Wip1 Phosphatase Involved in Lipopolysaccharide-Induced Neuroinflammation - Xiang Tan; Jingjing Zhang; Wei Jin; Lei Li; Wei Xu; Heyi Zheng; Ying Rui; Kaifu Ke; Ranran Zhou; Maohong Cao; Yongjin Pan (Journal of Molecular Neuroscience, 2013)

Elevated risk of opportunistic viral infection in patients with Crohn’s disease during biological therapies: a meta analysis of randomized controlled trials - Xiaobing Wang; Feng Zhou; Junzhang Zhao; Rui Zhou; Meifang Huang; Jin Li; Wei Wang; Shufang Xu; Bing Xia (European Journal of Clinical Pharmacology, 2013)

Hesperetin protects against cardiac remodelling induced by pressure overload in mice - Wei Deng; Duan Jiang; Yi Fang; Heng Zhou; Zhihong Cheng; Yafen Lin; Rui Zhang; Jieyu Zhang; Peng Pu; Yuan Liu; Zhouyan Bian; Qizhu Tang (Journal of Molecular Histology, 2013)

The member of high temperature requirement family HtrA2 participates in neuronal apoptosis after intracerebral hemorrhage in adult rats - Huiqing Sun; Lei Li; Feng Zhou; Lin Zhu; Kaifu Ke; Xiang Tan; Wei Xu; Ying Rui; Heyi Zheng; Zhengming Zhou; Huiguang Yang (Journal of Molecular Histology, 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Re–Os molybdenite ages and zircon Hf isotopes of the Gangjiang porphyry Cu–Mo deposit in the Tibetan Orogen - Cheng-Biao Leng; Xing-Chun Zhang; Hong Zhong; Rui-Zhong Hu; Wei-De Zhou; Chao Li (Mineralium Deposita, 2013)

Association of interleukin-1 receptor-associated kinase (IRAK1) gene polymorphisms (rs3027898, rs1059702) with systemic lupus erythematosus in a Chinese Han population - Yu Zhai; Ke Xu; Rui-Xue Leng; Han Cen; Wei Wang; Yan Zhu; Mo Zhou; Chen-Chen Feng; Dong-Qing Ye (Inflammation Research, 2013)

Association of AFF1 rs340630 and AFF3 rs10865035 polymorphisms with systemic lupus erythematosus in a Chinese population - Han Cen; Rui-Xue Leng; Wei Wang; Mo Zhou; Chen-Chen Feng; Gui-Mei Chen; Rui Li; Hai-Feng Pan; Xiang-Pei Li; Dong-Qing Ye (Immunogenetics, 2012)

Lihuaxuella thermophila gen. nov., sp. nov., isolated from a geothermal soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Bing-Huo Zhang; Ji-Cheng Yao; Shu-Kun Tang; En-Min Zhou; Yi-Rui Yin; Da-Qiao Wei; Hong Ming; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Lysobacter thermophilus sp. nov., isolated from a geothermal soil sample in Tengchong, south-west China - Da-Qiao Wei; Tian-Tian Yu; Ji-Cheng Yao; En-Min Zhou; Zhao-Qi Song; Yi-Rui Yin; Hong Ming; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

Characterization of a spliced variant of human IRF-3 promoter and its regulation by the transcription factor Sp1 - Wei Ren; Liang-Hua Zhu; Hua-Guo Xu; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2012)

Morphological and photosynthetic variations in the process of spermatia formation from vegetative cells in Porphyra yezoensis Ueda (Bangiales, Rhodophyta) and their responses to desiccation - Rui-Ling Yang; Wei Zhou; Song-Dong Shen; Guang-Ce Wang; Lin-Wen He; Guang-Hua Pan (Planta, 2012)

A New Piezochromic Fluorescence and Aggregation-Induced Emission Compound Containing Tetraphenylethylene and Triphenylamine Moieties with Morphology-alterable Property - Xie Zhou; Hai-yin Li; Zhen-guo Chi; Bing-jia Xu; Xi-qi Zhang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2012)

Transcriptional control of human CD2AP expression: the role of Sp1 and Sp3 - Hua-Guo Xu; Wei Ren; Li Zou; Yi Wang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2012)

Comparative proteomic and radiobiological analyses in human lung adenocarcinoma cells - Rui Wei; Yingjin Zhang; Liangfang Shen; Wuzhong Jiang; Cui Li; Meizuo Zhong; Yun Xie; Dingyi Yang; Lili He; Qing Zhou (Molecular and Cellular Biochemistry, 2012)

Characterization of a novel isoform of the human ORMDL3 gene - Rui Jin; Wen-Xiao Yuan; Hua-Guo Xu; Wei Ren; Li-Li Zhuang; Guo-Ping Zhou (Cell and Tissue Research, 2011)

The characterization of two novel IRF-3 transcripts starting from intron 2 of the wild type of IRF-3 - Wei Ren; Hua-Guo Xu; Chao Lu; Rui Jin; Li Zou; Yi Wang; Guo-Ping Zhou (Molecular Biology Reports, 2011)

Age-dependent expression of forkhead box O proteins in the duodenum of rats - Pan Huang; Zhen-qi Zhou; Rui-hua Huang; Bo Zhou; Quan-wei Wei; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2011)

Synthesis and Characterization of Triphenylethylene Derivatives with Aggregation-Induced Emission Characteristics - Xiao-Fang Li; Zhen-Guo Chi; Bing-Jia Xu; Hai-Yin Li; Xi-Qi Zhang; Wei Zhou; Yi Zhang; Si-Wei Liu; Jia-Rui Xu (Journal of Fluorescence, 2011)

Construction of the yeast whole-cell Rhizopus oryzae lipase biocatalyst with high activity - Mei-ling Chen; Qin Guo; Rui-zhi Wang; Juan Xu; Chen-wei Zhou; Hui Ruan; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2011)

Viral proteomics: The emerging cutting-edge of virus research - ShengTao Zhou; Rui Liu; Xia Zhao; CanHua Huang; YuQuan Wei (Science China Life Sciences, 2011)

Cloning and characterisation of a novel 2,4-dichlorophenol hydroxylase from a metagenomic library derived from polychlorinated biphenyl-contaminated soil - Yang Lu; Ying Yu; Rui Zhou; Wei Sun; Chunyan Dai; Pei Wan; Lanying Zhang; Dongyun Hao; Hejun Ren (Biotechnology Letters, 2011)

Direct repression of the human IRF-3 promoter by E2F1 - Hua-Guo Xu; Wei Ren; Li Zou; Yi Wang; Rui Jin; Guo-Ping Zhou (Immunogenetics, 2011)

Evaluation of Genetic Manipulation Strategies on d-Lactate Production by Escherichia coli - Li Zhou; Zhi-Rui Zuo; Xian-Zhong Chen; Dan-Dan Niu; Kang-Ming Tian; Bernard A. Prior; Wei Shen; Gui-Yang Shi; Suren Singh; Zheng-Xiang Wang (Current Microbiology, 2011)

Synthesis and Properties of Diphenylcarbazole Triphenylethylene Derivatives with Aggregation-Induced Emission, Blue Light Emission and High Thermal Stability - Bing-jia Xu; Zhen-guo Chi; Xiao-fang Li; Hai-yin Li; Wei Zhou; Xi-qi Zhang; Cheng-cheng Wang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Comparison of Responsive Behaviors of Two Cinnamic Acid Derivatives Containing Carbazolyl Triphenylethylene - Xi-qi Zhang; Zhen-guo Chi; Bing-jia Xu; Hai-yin Li; Wei Zhou; Xiao-fang Li; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

MicroRNA-17 post-transcriptionally regulates polycystic kidney disease-2 gene and promotes cell proliferation - Huan Sun; Qing-Wei Li; Xiao-Yan Lv; Jian-Zhong Ai; Qiu-Tan Yang; Jing-Jing Duan; Guo-Hui Bian; Yan Xiao; Yi-Dong Wang; Zheng Zhang; Yu-Hang Liu; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Fluorescent Property of the Gd3+-Doped Terbium Complexes and Crystal Structure of [Tb(TPTZ)(H2O)6]Cl3·3H2O - Yan-Fang Zhao; Yong-Liang Zhao; Feng Bai; Xiao-yan Wei; Yong-sheng Zhou; Mei-na Shan; Huan-huan Li; Rui-jun Ma; Xiao-tao Fu; Yan Du (Journal of Fluorescence, 2010)

Relationships Among Genetic Makeup, Active Ingredient Content, and Place of Origin of the Medicinal Plant Gastrodia Tuber - Jun Tao; Zhi-yong Luo; Chikira Ismail Msangi; Xiao-shun Shu; Li Wen; Shui-ping Liu; Chang-quan Zhou; Rui-xin Liu; Wei-xin Hu (Biochemical Genetics, 2009)

Loop-mediated isothermal amplification for rapid detection of Bacillus anthracis spores - Yan-Mei Qiao; Yong-Chao Guo; Xian-En Zhang; Ya-Feng Zhou; Zhi-Ping Zhang; Hong-Ping Wei; Rui-Fu Yang; Dian-Bing Wang (Biotechnology Letters, 2007)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)